Crystal of 5H-pyrrolo [2, 3-d] pyrimidine-6 (7H)-one and salt thereof
By discovering and preparing various stable crystal forms of compound (I) and crystals of hydrochloride and maleate, the stability of compound (I) in the prior art was solved, and its stability in pharmaceutical products was achieved Storage and low hygroscopicity.
Patent Information
- Application Number
- CN202380051803.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-07-05
- Filing Date
- 2023-07-04
- Publication Date
- 2025-02-07
AI Technical Summary
The prior art lacks stable crystallization of compound (I) and its preparation method, which affects its stability and storage management as a pharmaceutical product.
Three crystal forms (type I, type II, type III) of the free body of compound (I) and their hydrochloride and maleate were discovered and prepared, and the crystals were obtained by powder X-ray diffraction spectrum and thermal gravimetric difference. Thermal synchronization measurement and other methods verify its stability and low hygroscopicity.
It provides a stable crystal form of compound (I), which improves its solid stability and low hygroscopicity, making it more suitable for use as a pharmaceutical original drug.
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] The present invention relates to a crystal of 4-(4-(3-((2-(tert-butylamino)ethyl)amino)-6-(5-(trifluoromethyl)-1,3,4-oxadiazol-2-yl)pyridin-2-yl)piperidin-1-yl)-5,5-dimethyl-5H-pyrrolo[2,3-d]pyrimidin-6(7H)-one and a salt thereof which has excellent storage stability and hygroscopicity and is useful as a pharmaceutical or a pharmaceutical raw material. Background Art
[0002] Generally, when a compound is used as an effective active ingredient of a pharmaceutical product, chemical and physical stability of the compound is required in order to maintain stable quality and / or facilitate storage management.
[0003] Patent Document 1 describes 4-(4-(3-((2-(tert-butylamino)ethyl)amino)-6-(5-(trifluoromethyl)-1,3,4-oxadiazol-2-yl)pyridin-2-yl)piperidin-1-yl)-5,5-dimethyl-5H-pyrrolo[2,3-d]pyrimidin-6(7H)-one (hereinafter also referred to as “Compound (I)”) represented by the following formula (I) as a medically useful compound having excellent inhibitory activity against at least one selected from Akt, Rsk and S6K and / or a cancer cell proliferation inhibitory effect and / or for treating various diseases (particularly cancer) in which at least one selected from Akt, Rsk and S6K is involved.
[0004] However, Patent Document 1 does not describe the crystal form of the compound, and a stable crystal of Compound (I) and a method for producing the same are not known to date.
[0005] Prior art literature Patent Literature Patent Document 1: International Publication No. 2017 / 200087 Summary of the invention
[0006] Problems to be solved by the invention An object of the present invention is to provide a crystal of a free form of a compound (I) or a crystal of a salt thereof which is useful as a pharmaceutical or a pharmaceutical raw material.
[0007] Technical solutions to solve problems In order to solve the above problems, intensive studies were conducted, and as a result, three crystal forms (type I crystal, type II crystal, type III crystal) were found as the free form of compound (I). Crystals of the hydrochloride salt and the maleate salt of compound (I) were also found. These crystals were found to have excellent solid stability and / or low hygroscopicity.
[0008] That is, the present invention provides the following [1] to
[32] .
[0009] [1] A type I crystal of a free form of 4-(4-(3-((2-(tert-butylamino)ethyl)amino)-6-(5-(trifluoromethyl)-1,3,4-oxadiazol-2-yl)pyridin-2-yl)piperidin-1-yl)-5,5-dimethyl-5H-pyrrolo[2,3-d]pyrimidin-6(7H)-one, which has peaks at at least two diffraction angles (2θ±0.2°) selected from the following (a) and at least two diffraction angles (2θ±0.2°) selected from the following (b) in a powder X-ray diffraction spectrum (CuKα): (a) 6.2°, 9.3°, 9.7°, 11.1°, 15.4° and 25.1°; (b) 6.7°, 8.3°, 8.7°, 13.0°, 13.7°, 16.3°, 16.9°, 17.7°, 18.7°, 19.4°, 20.3°, 25.9° and 26.5°.
[0010] [2] The type I crystal of the free form described in [1], which has peaks at at least three diffraction angles (2θ±0.2°) selected from the following (a) and at least four diffraction angles (2θ±0.2°) selected from the following (b) in a powder X-ray diffraction spectrum (CuKα): (a) 6.2°, 9.3°, 9.7°, 11.1°, 15.4° and 25.1°; (b) 6.7°, 8.3°, 8.7°, 13.0°, 13.7°, 16.3°, 16.9°, 17.7°, 18.7°, 19.4°, 20.3°, 25.9° and 26.5°.
[0011] [3] The free form I crystal according to [1], which has a peak at the following diffraction angle (2θ±0.2°) in the powder X-ray diffraction spectrum (CuKα): 6.2°, 6.7°, 8.3°, 8.7°, 9.3°, 9.7°, 11.1°, 13.0°, 13.7°, 15.4°, 16.3°, 16.9°, 17.7°, 18.7°, 19.4°, 20.3°, 25.1°, 25.9°, and 26.5°.
[0012] [4] The free form I crystal as described in [1], which has Figure 1 The powder X-ray diffraction spectrum shown is substantially the same as the powder X-ray diffraction spectrum of the crystals.
[0013] [5] The free form type I crystal according to [1], which has an endothermic peak with a peak temperature of around 235° C. in thermogravimetric-differential thermal analysis (TG-DTA analysis).
[0014] [6] A pharmaceutical composition comprising the type I crystal of the free form according to any one of [1] to [5].
[0015] [7] A method for producing a type I crystal of the free form described in [1], comprising: a step of dissolving 4-(4-(3-((2-(tert-butylamino)ethyl)amino)-6-(5-(trifluoromethyl)-1,3,4-oxadiazol-2-yl)pyridin-2-yl)piperidin-1-yl)-5,5-dimethyl-5H-pyrrolo[2,3-d]pyrimidin-6(7H)-one in a solvent 1; and a step of adding a solvent 2 to the obtained solution to obtain 4-(4-(3-((2-(tert-butylamino)ethyl)amino)-6-(5-(trifluoromethyl)-1,3,4-oxadiazol-2-yl)pyridin-2-yl)piperidin-1-yl)-5,5-dimethyl-5H-pyrrolo[2,3-d]pyrimidin-6(7H)-one.
[0016] [8] The method as described in [7], wherein solvent 1 is dimethyl sulfoxide and solvent 2 is water, or solvent 1 is tetrahydrofuran and solvent 2 is n-heptane, ethyl acetate or 2-propanol.
[0017] [9] The method as described in [7], wherein solvent 1 is dimethyl sulfoxide and solvent 2 is water.
[0018]
[10] A free form type I crystal according to [1], obtained by the steps of dissolving 4-(4-(3-((2-(tert-butylamino)ethyl)amino)-6-(5-(trifluoromethyl)-1,3,4-oxadiazol-2-yl)pyridin-2-yl)piperidin-1-yl)-5,5-dimethyl-5H-pyrrolo[2,3-d]pyrimidin-6(7H)-one in dimethyl sulfoxide; and adding water to the obtained solution to obtain 4-(4-(3-((2-(tert-butylamino)ethyl)amino)-6-(5-(trifluoromethyl)-1,3,4-oxadiazol-2-yl)pyridin-2-yl)piperidin-1-yl)-5,5-dimethyl-5H-pyrrolo[2,3-d]pyrimidin-6(7H)-one and crystallizing the resulting solution.
[0019]
[11] A type II crystal of a free form of 4-(4-(3-((2-(tert-butylamino)ethyl)amino)-6-(5-(trifluoromethyl)-1,3,4-oxadiazol-2-yl)pyridin-2-yl)piperidin-1-yl)-5,5-dimethyl-5H-pyrrolo[2,3-d]pyrimidin-6(7H)-one, which has peaks at at least two diffraction angles (2θ±0.2°) selected from the following (a) and at least two diffraction angles (2θ±0.2°) selected from the following (b) in a powder X-ray diffraction spectrum (CuKα): (a) 10.4°, 22.9° and 27.9°; (b) 6.7°, 7.5°, 12.7°, 13.4°, 14.6°, 16.5°, 17.9°, 18.3°, 19.8°, 20.6°, 21.8° and 26.5°.
[0020]
[12] The free form type II crystal according to
[11] , which has peaks at at least three diffraction angles (2θ±0.2°) selected from the following (a), and at least four diffraction angles (2θ±0.2°) selected from the following (b) in a powder X-ray diffraction spectrum (CuKα): (a) 10.4°, 22.9° and 27.9°; (b) 6.7°, 7.5°, 12.7°, 13.4°, 14.6°, 16.5°, 17.9°, 18.3°, 19.8°, 20.6°, 21.8° and 26.5°.
[0021]
[13] The type II crystal of the free form as described in
[11] , which has a peak at the following diffraction angle (2θ±0.2°) in the powder X-ray diffraction spectrum (CuKα): 6.7°, 7.5°, 10.4°, 12.7°, 13.4°, 14.6°, 16.5°, 17.9°, 18.3°, 19.8°, 20.6°, 21.8°, 22.9°, 26.5° and 27.9°.
[0022]
[14] The free form II crystal as described in
[11] , which has Figure 3 The powder X-ray diffraction spectrum shown is substantially the same as the powder X-ray diffraction spectrum of the crystals.
[0023]
[15] The free form type II crystal according to
[11] , which has an endothermic peak with a peak temperature of around 234° C. in thermogravimetric-differential thermal analysis (TG-DTA analysis).
[0024]
[16] A pharmaceutical composition comprising the type II crystal of the free form according to any one of
[11] to
[15] .
[0025]
[17] A type III crystal of a free form of 4-(4-(3-((2-(tert-butylamino)ethyl)amino)-6-(5-(trifluoromethyl)-1,3,4-oxadiazol-2-yl)pyridin-2-yl)piperidin-1-yl)-5,5-dimethyl-5H-pyrrolo[2,3-d]pyrimidin-6(7H)-one, which has peaks at at least two diffraction angles (2θ±0.2°) selected from the following (a) and at least two diffraction angles (2θ±0.2°) selected from the following (b) in a powder X-ray diffraction spectrum (CuKα): (a) 11.7°, 23.4° and 24.2°; (b) 6.8°, 7.5°, 8.8°, 12.9°, 13.9°, 14.9°, 16.7°, 17.8°, 18.8°, 19.7°, 20.7°, 22.0°, 26.2° and 26.7°.
[0026]
[18] The free form type III crystal according to
[17] , which has peaks at three diffraction angles (2θ±0.2°) selected from the following (a) and at least four diffraction angles (2θ±0.2°) selected from the following (b) in a powder X-ray diffraction spectrum (CuKα): (a) 11.7°, 23.4° and 24.2°; (b) 6.8°, 7.5°, 8.8°, 12.9°, 13.9°, 14.9°, 16.7°, 17.8°, 18.8°, 19.7°, 20.7°, 22.0°, 26.2° and 26.7°.
[0027]
[19] The free form type III crystal according to
[17] , which has a peak at the following diffraction angle (2θ±0.2°) in the powder X-ray diffraction spectrum (CuKα): 6.8°, 7.5°, 8.8°, 11.7°, 12.9°, 13.9°, 14.9°, 16.7°, 17.8°, 18.8°, 19.7°, 20.7°, 22.0°, 23.4°, 24.2°, 26.2° and 26.7°.
[0028]
[20] The free form III crystal as described in
[17] , which has Figure 5 The powder X-ray diffraction spectrum shown is substantially the same as the powder X-ray diffraction spectrum of the crystals.
[0029]
[21] The free-form type III crystal according to
[17] , which has an endothermic peak with a peak temperature of around 234° C. in thermogravimetric-differential thermal analysis (TG-DTA analysis).
[0030]
[22] A pharmaceutical composition comprising the type III crystal of the free form according to any one of
[17] to
[21] .
[0031]
[23] A crystal of the hydrochloride salt of 4-(4-(3-((2-(tert-butylamino)ethyl)amino)-6-(5-(trifluoromethyl)-1,3,4-oxadiazol-2-yl)pyridin-2-yl)piperidin-1-yl)-5,5-dimethyl-5H-pyrrolo[2,3-d]pyrimidin-6(7H)-one, which has peaks at at least three diffraction angles (2θ±0.2°) selected from the following in a powder X-ray diffraction spectrum (CuKα): 6.7°, 7.4°, 11.2°, 12.6°, 14.1°, 16.6°, 20.0°, 21.1°, 22.0°, 22.6°, 23.2°, 24.5°, 26.4°, 28.0°, 30.0° and 31.6°.
[0032]
[24] The hydrochloride crystals according to
[23] , which have a peak at the following diffraction angle (2θ±0.2°) in the powder X-ray diffraction spectrum (CuKα): 6.7°, 7.4°, 11.2°, 12.6°, 14.1°, 16.6°, 20.0°, 21.1°, 22.0°, 22.6°, 23.2°, 24.5°, 26.4°, 28.0°, 30.0° and 31.6°.
[0033]
[25] The crystal of the hydrochloride salt as described in
[23] , which has Figure 7 The powder X-ray diffraction spectrum shown is substantially the same as the powder X-ray diffraction spectrum of the crystals.
[0034]
[26] The crystal of the hydrochloride according to
[23] , which has an endothermic peak with a peak temperature of about 241° C. in thermogravimetric-differential thermal analysis (TG-DTA analysis).
[0035]
[27] A pharmaceutical composition comprising a crystal of the hydrochloride according to any one of
[23] to
[26] .
[0036]
[28] A crystal of a maleate salt of 4-(4-(3-((2-(tert-butylamino)ethyl)amino)-6-(5-(trifluoromethyl)-1,3,4-oxadiazol-2-yl)pyridin-2-yl)piperidin-1-yl)-5,5-dimethyl-5H-pyrrolo[2,3-d]pyrimidin-6(7H)-one, which has peaks at at least three diffraction angles (2θ±0.2°) selected from the following in a powder X-ray diffraction spectrum (CuKα): 6.5°, 9.8°, 12.1°, 13.0°, 13.9°, 14.7°, 15.2°, 15.9°, 17.7°, 18.4°, 19.0°, 20.1°, 20.9°, 21.5°, 22.9°, 23.4°, 25.3°, 28.0°, 29.7° and 30.8°.
[0037]
[29] The crystal of the maleate salt described in
[28] , which has a peak at the following diffraction angle (2θ±0.2°) in the powder X-ray diffraction spectrum (CuKα): 6.5°, 9.8°, 12.1°, 13.0°, 13.9°, 14.7°, 15.2°, 15.9°, 17.7°, 18.4°, 19.0°, 20.1°, 20.9°, 21.5°, 22.9°, 23.4°, 25.3°, 28.0°, 29.7° and 30.8°.
[0038]
[30] The crystal of the maleate salt as described in
[28] , which has Fig. 9 The powder X-ray diffraction spectrum shown is substantially the same as the powder X-ray diffraction spectrum of the crystals.
[0039]
[31] The crystal of the maleate salt according to
[28] , which has an endothermic peak with a peak temperature of about 245° C. in thermogravimetric-differential thermal analysis (TG-DTA analysis).
[0040]
[32] A pharmaceutical composition comprising a crystal of the maleate salt according to any one of
[28] to
[31] .
[0041] The present invention also provides the following
[33] to
[60] .
[0042]
[33] A method for treating tumors, comprising the step of administering the pharmaceutical composition described in [6] to a subject.
[0043]
[34] A method for treating tumors, comprising the step of administering the pharmaceutical composition described in
[16] to a subject.
[0044]
[35] A method for treating tumors, comprising the step of administering the pharmaceutical composition described in
[22] to a subject.
[0045]
[36] A method for treating tumors, comprising the step of administering the pharmaceutical composition described in
[27] to a subject.
[0046]
[37] A method for treating tumors, comprising the step of administering the pharmaceutical composition described in
[32] to a subject.
[0047]
[38] A type I crystal of a free form of 4-(4-(3-((2-(tert-butylamino)ethyl)amino)-6-(5-(trifluoromethyl)-1,3,4-oxadiazol-2-yl)pyridin-2-yl)piperidin-1-yl)-5,5-dimethyl-5H-pyrrolo[2,3-d]pyrimidin-6(7H)-one for use in the treatment of a tumor, which has peaks at at least two diffraction angles (2θ±0.2°) selected from the following (a) and at least two diffraction angles (2θ±0.2°) selected from the following (b) in a powder X-ray diffraction spectrum (CuKα): (a) 6.2°, 9.3°, 9.7°, 11.1°, 15.4° and 25.1°; (b) 6.7°, 8.3°, 8.7°, 13.0°, 13.7°, 16.3°, 16.9°, 17.7°, 18.7°, 19.4°, 20.3°, 25.9° and 26.5°.
[0048]
[39] The type I crystal of the free form described in
[38] , which has peaks at at least three diffraction angles (2θ±0.2°) selected from the following (a), and at least four diffraction angles (2θ±0.2°) selected from the following (b) in a powder X-ray diffraction spectrum (CuKα): (a) 6.2°, 9.3°, 9.7°, 11.1°, 15.4° and 25.1°; (b) 6.7°, 8.3°, 8.7°, 13.0°, 13.7°, 16.3°, 16.9°, 17.7°, 18.7°, 19.4°, 20.3°, 25.9° and 26.5°.
[0049]
[40] The type I crystal of the free form described in
[38] , which has a peak at the following diffraction angle (2θ±0.2°) in the powder X-ray diffraction spectrum (CuKα): 6.2°, 6.7°, 8.3°, 8.7°, 9.3°, 9.7°, 11.1°, 13.0°, 13.7°, 15.4°, 16.3°, 16.9°, 17.7°, 18.7°, 19.4°, 20.3°, 25.1°, 25.9°, and 26.5°.
[0050]
[41] The free form I crystal as described in
[38] , which has Figure 1 The powder X-ray diffraction spectrum shown is substantially the same as the powder X-ray diffraction spectrum of the crystals.
[0051]
[42] The free form type I crystal according to
[38] , which has an endothermic peak with a peak temperature of around 235° C. in thermogravimetric-differential thermal analysis (TG-DTA analysis).
[0052]
[43] A type II crystal of a free form of 4-(4-(3-((2-(tert-butylamino)ethyl)amino)-6-(5-(trifluoromethyl)-1,3,4-oxadiazol-2-yl)pyridin-2-yl)piperidin-1-yl)-5,5-dimethyl-5H-pyrrolo[2,3-d]pyrimidin-6(7H)-one for use in the treatment of a tumor, which has peaks at at least two diffraction angles (2θ±0.2°) selected from the following (a) and at least two diffraction angles (2θ±0.2°) selected from the following (b) in a powder X-ray diffraction spectrum (CuKα): (a) 10.4°, 22.9° and 27.9°; (b) 6.7°, 7.5°, 12.7°, 13.4°, 14.6°, 16.5°, 17.9°, 18.3°, 19.8°, 20.6°, 21.8° and 26.5°.
[0053]
[44] The type II crystal of the free form described in
[43] , which has peaks at at least four diffraction angles (2θ±0.2°) selected from the following (b): (a) 10.4°, 22.9° and 27.9°; (b) 6.7°, 7.5°, 12.7°, 13.4°, 14.6°, 16.5°, 17.9°, 18.3°, 19.8°, 20.6°, 21.8° and 26.5°.
[0054]
[45] The type II crystal of the free form described in
[43] , which has a peak at the following diffraction angle (2θ±0.2°) in the powder X-ray diffraction spectrum (CuKα): 6.7°, 7.5°, 10.4°, 12.7°, 13.4°, 14.6°, 16.5°, 17.9°, 18.3°, 19.8°, 20.6°, 21.8°, 22.9°, 26.5° and 27.9°.
[0055]
[46] The free form II crystal as described in
[43] , which has Figure 3 The powder X-ray diffraction spectrum shown is substantially the same as the powder X-ray diffraction spectrum of the crystals.
[0056]
[47] The free form type II crystal according to
[43] , which has an endothermic peak with a peak temperature of around 234° C. in thermogravimetric-differential thermal analysis (TG-DTA analysis).
[0057]
[48] A type III crystal of a free form of 4-(4-(3-((2-(tert-butylamino)ethyl)amino)-6-(5-(trifluoromethyl)-1,3,4-oxadiazol-2-yl)pyridin-2-yl)piperidin-1-yl)-5,5-dimethyl-5H-pyrrolo[2,3-d]pyrimidin-6(7H)-one for use in the treatment of a tumor, which has peaks at at least two diffraction angles (2θ±0.2°) selected from the following (a) and at least two diffraction angles (2θ±0.2°) selected from the following (b) in a powder X-ray diffraction spectrum (CuKα): (a) 11.7°, 23.4° and 24.2°; (b) 6.8°, 7.5°, 8.8°, 12.9°, 13.9°, 14.9°, 16.7°, 17.8°, 18.8°, 19.7°, 20.7°, 22.0°, 26.2° and 26.7°.
[0058]
[49] The type III crystal of the free form described in
[48] , which has peaks at at least four diffraction angles (2θ±0.2°) selected from the following (b): (a) 11.7°, 23.4° and 24.2°; (b) 6.8°, 7.5°, 8.8°, 12.9°, 13.9°, 14.9°, 16.7°, 17.8°, 18.8°, 19.7°, 20.7°, 22.0°, 26.2° and 26.7°.
[0059]
[50] The type III crystal of the free form described in
[48] , which has a peak at the following diffraction angle (2θ±0.2°) in the powder X-ray diffraction spectrum (CuKα): 6.8°, 7.5°, 8.8°, 11.7°, 12.9°, 13.9°, 14.9°, 16.7°, 17.8°, 18.8°, 19.7°, 20.7°, 22.0°, 23.4°, 24.2°, 26.2° and 26.7°.
[0060]
[51] The free form III crystal as described in
[48] , which has Figure 5 The powder X-ray diffraction spectrum (CuKα) shown is substantially the same as the powder X-ray diffraction spectrum of the crystals.
[0061]
[52] The free-form type III crystal according to
[48] , which has an endothermic peak with a peak temperature of around 234° C. in thermogravimetric-differential thermal analysis (TG-DTA analysis).
[0062]
[53] A crystal of a hydrochloride of a free form of 4-(4-(3-((2-(tert-butylamino)ethyl)amino)-6-(5-(trifluoromethyl)-1,3,4-oxadiazol-2-yl)pyridin-2-yl)piperidin-1-yl)-5,5-dimethyl-5H-pyrrolo[2,3-d]pyrimidin-6(7H)-one for use in the treatment of a tumor, wherein the crystal has peaks at at least three diffraction angles (2θ±0.2°) selected from the following diffraction angles in a powder X-ray diffraction spectrum (CuKα): 6.7°, 7.4°, 11.2°, 12.6°, 14.1°, 16.6°, 20.0°, 21.1°, 22.0°, 22.6°, 23.2°, 24.5°, 26.4°, 28.0°, 30.0° and 31.6°.
[0063]
[54] The hydrochloride crystals according to
[52] , which have a peak at the following diffraction angle (2θ±0.2°) in the powder X-ray diffraction spectrum (CuKα): 6.7°, 7.4°, 11.2°, 12.6°, 14.1°, 16.6°, 20.0°, 21.1°, 22.0°, 22.6°, 23.2°, 24.5°, 26.4°, 28.0°, 30.0° and 31.6°.
[0064]
[55] The hydrochloride crystals as described in
[53] , which have Figure 7 The powder X-ray diffraction spectrum shown is substantially the same as the powder X-ray diffraction spectrum of the crystals.
[0065]
[56] The crystal of the hydrochloride according to
[53] , which has an endothermic peak with a peak temperature of about 241° C. in thermogravimetric-differential thermal analysis (TG-DTA analysis).
[0066]
[57] A crystal of a free form maleate of 4-(4-(3-((2-(tert-butylamino)ethyl)amino)-6-(5-(trifluoromethyl)-1,3,4-oxadiazol-2-yl)pyridin-2-yl)piperidin-1-yl)-5,5-dimethyl-5H-pyrrolo[2,3-d]pyrimidin-6(7H)-one for use in the treatment of a tumor, wherein the crystal has peaks at at least three diffraction angles (2θ±0.2°) selected from the following diffraction angles in a powder X-ray diffraction spectrum (CuKα): 6.5°, 9.8°, 12.1°, 13.0°, 13.9°, 14.7°, 15.2°, 15.9°, 17.7°, 18.4°, 19.0°, 20.1°, 20.9°, 21.5°, 22.9°, 23.4°, 25.3°, 28.0°, 29.7° and 30.8°.
[0067]
[58] The crystal of the maleate salt described in
[57] , which has a peak at the following diffraction angle (2θ±0.2°) in the powder X-ray diffraction spectrum (CuKα): 6.5°, 9.8°, 12.1°, 13.0°, 13.9°, 14.7°, 15.2°, 15.9°, 17.7°, 18.4°, 19.0°, 20.1°, 20.9°, 21.5°, 22.9°, 23.4°, 25.3°, 28.0°, 29.7° and 30.8°.
[0068]
[59] The crystal of the maleate salt as described in
[57] , which has Fig. 9 The powder X-ray diffraction spectrum shown is substantially the same as the powder X-ray diffraction spectrum of the crystals.
[0069]
[60] The crystal of the maleate salt according to
[57] , which has an endothermic peak with a peak temperature of about 245° C. in thermogravimetric-differential thermal analysis (TG-DTA analysis).
[0070] Effects of the Invention According to the present invention, a stable crystalline form of the above-mentioned compound (I) useful as a compound having an antitumor effect is provided. In addition, the stable crystalline form of the compound (I) of the present invention and its preparation method are not known at present. In the present invention, the crystalline form (type I crystal, type II crystal, type III crystal) of the free form of the compound (I), the crystal of the hydrochloride salt, and the crystal of the maleate salt are superior to other crystalline forms, for example, from the viewpoint of low hygroscopicity and / or solid stability, and therefore are useful forms when the compound is used as a raw drug for pharmaceuticals. BRIEF DESCRIPTION OF THE DRAWINGS
[0071] Figure 1 This shows the powder X-ray diffraction spectrum (CuKα) of the type I crystal of the free form of compound (I) obtained in Example 1 (the vertical axis represents the intensity (counts), and the horizontal axis represents the diffraction angle (2θ)).
[0072] Figure 2 This is a thermogravimetric-differential thermal analysis (TG-DTA analysis) curve of the type I crystal of the free form of compound (I) obtained in Example 1.
[0073] Figure 3This shows the powder X-ray diffraction spectrum (CuKα) of the type II crystal of the free form of compound (I) obtained in Example 2 (the vertical axis represents the intensity (counts), and the horizontal axis represents the diffraction angle (2θ)).
[0074] Figure 4 This is a thermogravimetric-differential thermal analysis (TG-DTA analysis) curve of the type II crystal of the free form of compound (I) obtained in Example 2.
[0075] Figure 5 This shows the powder X-ray diffraction spectrum (CuKα) of the type III crystal of the free form of compound (I) obtained in Example 3 (the vertical axis represents the intensity (counts), and the horizontal axis represents the diffraction angle (2θ)).
[0076] Figure 6 This is a thermogravimetric-differential thermal analysis (TG-DTA analysis) curve of the type III crystal of the free form of compound (I) obtained in Example 3.
[0077] Figure 7 This shows a powder X-ray diffraction spectrum (CuKα) of the crystals of the hydrochloride of Compound (I) obtained in Example 4 (the vertical axis represents the intensity (counts), and the horizontal axis represents the diffraction angle (2θ)).
[0078] Figure 8 This is a thermogravimetric-differential thermal analysis (TG-DTA analysis) curve of the crystal of the hydrochloride salt of Compound (I) obtained in Example 4.
[0079] Fig. 9 The figure shows the powder X-ray diffraction spectrum (CuKα) of the crystal of the maleate salt of Compound (I) obtained in Example 5 (the vertical axis represents the intensity (counts), and the horizontal axis represents the diffraction angle (2θ)).
[0080] Fig.10 This is a thermogravimetric-differential thermal analysis (TG-DTA analysis) curve of the crystal of the maleate salt of Compound (I) obtained in Example 5.
[0081] Fig.11 The figure shows the powder X-ray diffraction spectrum (CuKα) of the crystal of 1 / 2 malate of Compound (I) obtained in Comparative Example 1 (the vertical axis represents the intensity (counts), and the horizontal axis represents the diffraction angle (2θ)).
[0082] Fig.12 This is a thermogravimetric-differential thermal analysis (TG-DTA analysis) curve of the crystal of 1 / 2 malate of Compound (I) obtained in Comparative Example 1.
[0083] Fig.13The figure shows the powder X-ray diffraction spectrum (CuKα) of the crystals of the acetate salt of Compound (I) obtained in Comparative Example 2 (the vertical axis represents the intensity (counts), and the horizontal axis represents the diffraction angle (2θ)).
[0084] Fig.14 This is a thermogravimetric-differential thermal analysis (TG-DTA analysis) curve of the crystals of the acetate salt of Compound (I) obtained in Comparative Example 2.
[0085] Fig.15 This figure shows the water adsorption-desorption isotherm of the type I crystal of the free form of compound (I) obtained in Example 1.
[0086] Fig.16 This figure shows the water adsorption-desorption isotherm of the type II crystal of the free form of compound (I) obtained in Example 2.
[0087] Fig.17 This figure shows the water adsorption-desorption isotherm of the type III crystal of the free form of compound (I) obtained in Example 3.
[0088] Fig.18 This shows the powder X-ray diffraction data of the type I crystal of the free form of compound (I) obtained in Example 1 at 25°C.
[0089] Fig.19 This shows the powder X-ray diffraction data of the type I crystal of the free form of compound (I) obtained in Example 1 at 210°C.
[0090] Fig. 20 This shows the powder X-ray diffraction data of the type II crystal of the free form of compound (I) obtained in Example 2 at 25°C.
[0091] Fig.21 This shows the powder X-ray diffraction data of the type II crystal of the free form of compound (I) obtained in Example 2 at 210°C.
[0092] Fig. 22 This shows the powder X-ray diffraction data of the type III crystal of the free form of compound (I) obtained in Example 3 at 25°C.
[0093] Fig.23 This shows the powder X-ray diffraction data of the type III crystal of the free form of compound (I) obtained in Example 3 at 210°C.
[0094] Fig.24 The water adsorption-desorption isotherm of the crystals of the hydrochloride salt of Compound (I) obtained in Example 4 is shown.
[0095] Fig.25The water adsorption-desorption isotherm of the crystals of the maleate salt of Compound (I) obtained in Example 5 is shown.
[0096] Fig.26 The water adsorption-desorption isotherm of the crystal of 1 / 2 malate of Compound (I) obtained in Comparative Example 1 is shown.
[0097] Fig. 27 The water adsorption-desorption isotherm of the crystals of the acetate salt of Compound (I) obtained in Comparative Example 2 is shown. DETAILED DESCRIPTION
[0098] In the present specification, “Compound (I)” alone refers to 4-(4-(3-((2-(tert-butylamino)ethyl)amino)-6-(5-(trifluoromethyl)-1,3,4-oxadiazol-2-yl)pyridin-2-yl)piperidin-1-yl)-5,5-dimethyl-5H-pyrrolo[2,3-d]pyrimidin-6(7H)-one, and is used to include both “amorphous” and “crystalline” forms.
[0099] In the salt form of Compound (I), the molar equivalent of the acid relative to Compound (I) can be analyzed by, for example, NMR or liquid chromatography.
[0100] In the present invention, when the crystal is recorded as a hydrochloride, maleate or acetate of compound (I), it is a salt in which the molar ratio of compound (I) to hydrochloric acid, maleic acid or acetic acid is 1:1, which can be determined by analysis such as 1H-NMR. Generally, in a salt of an organic compound, the molar ratio of the acid to the organic compound can be determined by comparing the integral value of the protons of the methyl group of the acid with the integral value of at least one proton of the organic compound. It is known that the integral value of the proton will produce an error by correction of the baseline of the 1H-NMR spectrum, so in the range of 0.8 to 1.2:1, the molar ratio of the acid to the organic compound can be regarded as 1:1.
[0101] Compound (I) can be synthesized, for example, according to the method described in International Publication No. 2017 / 200087 (for example, the method described in Example 32 of the publication), but is not limited to this method.
[0102] When used in this specification, and unless otherwise specified, the term "crystal" and related terms used in this specification, when used to describe a compound, substance, modification, material, component or product, means that the compound, substance, modification, material, component or product is substantially crystalline when determined by X-ray diffraction. For example, reference can be made to Remington: The Science and Practice of Pharmacy, 21st edition, Lippincott, Williams and Wilkins, Baltimore, MD (2005); United States Pharmacopoeia, 23rd edition, 1843-1844 (1995). "Crystal" includes hydrates or solvates (pseudopolymorphs), cocrystals. In this specification, the terms "crystal" and "crystalline form" can be used interchangeably.
[0103] In the art, it is known that even in a multi-component system that can form a salt (with proton transfer caused by acid or base reaction), the main component (original drug) and the secondary components (coformer, counter ion, solvent) are sometimes in a state of forming a complex through weak intermolecular interactions such as hydrogen bonds (e.g., Cryst. Growth Des. 2012, 12, 2147-2152 dx.doi.org / 10.1021 / cg3002948).
[0104] The "crystal" of the "salt" in the present invention also includes a crystal of a complex formed of such a plurality of components ("eutectic").
[0105] As used herein, and unless otherwise specifically stated, the terms "amorphous", "amorphous form" and related terms used herein mean that the substance, component or product is not substantially crystalline as determined by X-ray diffraction. In particular, the term "amorphous form" describes an irregular solid form, i.e. a solid form lacking long-range crystalline order.
[0106] The term "pharmaceutically acceptable salt" refers to salts derived from various organic and inorganic counterions known in the art. Pharmaceutically acceptable salts are safe for animals or humans to ingest.
[0107] As a technique for characterizing the crystalline form and the amorphous form, it is not limited, and thermogravimetric analysis (TGA), differential scanning calorimetry (DSC), X-ray powder diffraction (XRPD), single crystal X-ray diffraction, vibration spectroscopy, for example, infrared (IR) and Raman spectroscopy, solid nuclear magnetic resonance (NMR) spectroscopy, optical microscope observation, hot stage optical microscope observation, scanning electron microscope observation (SEM), electron beam crystallography and quantitative analysis, solubility determination and other well-known techniques in the art can be used. Characteristic unit cell parameters are not limited, and can be determined using one or more techniques represented by single crystal diffraction and powder diffraction, X-ray diffraction and neutron diffraction. As a useful technique for analyzing powder diffraction data, profile refinement such as Rietveld refinement can be listed, which can be used to analyze the diffraction peaks related to a single phase in a sample containing two or more solid phases. As other methods useful for analyzing powder diffraction data, unit cell indexing can be listed, which enables a person skilled in the art to determine unit cell parameters from a sample containing crystalline powder.
[0108] In addition, in the powder X-ray diffraction spectrum, the diffraction angle and the entire spectrum are important in determining the identity of the crystal in terms of the nature of the data. The relative intensity of the powder X-ray diffraction spectrum will slightly change depending on the direction of crystal growth, particle size, and measurement conditions, and should not be strictly interpreted.
[0109] The crystal can be identified by the peak in the powder X-ray diffraction spectrum. Among them, the "peak" is selected from the peak having an intensity of 5% or more, 6% or more, 7% or more, 8% or more, 9% or more, 10% or more, 15% or more, or 20% or more of the maximum peak intensity in the intensity peak obtained by the powder X-ray diffraction spectrum (CuKα). Sometimes, a peak having an intensity of more preferably 5% or more of the intensity of the maximum peak in the obtained intensity peak, more preferably 6% or more of the intensity of the maximum peak in the obtained intensity peak, more preferably 7% or more of the intensity of the maximum peak in the obtained intensity peak, more preferably 8% or more of the intensity of the maximum peak in the obtained intensity peak, more preferably 9% or more of the intensity of the maximum peak in the obtained intensity peak, more preferably 10% or more of the intensity of the maximum peak in the obtained intensity peak, further preferably 15% or more of the intensity of the maximum peak in the obtained intensity peak, and particularly preferably 20% or more of the intensity of the maximum peak in the obtained intensity peak is selected.
[0110] The values obtained from various patterns may have some errors depending on the direction of crystal growth, particle size, measurement conditions, etc. Therefore, in this specification, the values of diffraction angles (2θ) in the powder X-ray diffraction patterns may have a measurement error within a range of about ±0.2°.
[0111] In addition, the endothermic peak in the thermogravimetric-differential thermal simultaneous measurement (TG-DTA measurement) curve may change the measurement temperature due to the temperature rise amplitude per minute, the purity of the sample, etc. In this specification, the term "near" in the TG-DTA measurement temperature value refers to the temperature value within ±2, 3, 4 or 5°C of the value. As the temperature range, it is preferably ±5°C, more preferably ±4°C, further preferably ±3°C, and particularly preferably ±2°C.
[0112] In one embodiment, the crystalline form of compound (I) disclosed in the present specification may include multiple crystals (crystalline polymorphs) having spatially regular atomic configurations and may produce different physicochemical properties. In one embodiment, the crystalline form disclosed in the present specification may be a mixture containing crystalline polymorphs.
[0113] The crystal form of the compound (I) of the present invention may be characterized by a combination of the following embodiments, which are not contradictory to each other. For example, the crystal form of the compound (I) may be characterized by a combination of the above-mentioned peaks in the X-ray diffraction spectrum and the above-mentioned endothermic peaks measured by TG-DTA.
[0114] Compounds labeled with isotopes (eg, deuterium, 3H, 14C, 35S, 125I, etc.) are also included in the compounds described in the present specification or pharmaceutically acceptable salts thereof.
[0115] The crystalline forms of some compounds (I) disclosed in this specification are stable when exposed to conditions of about 1, 2, 3, 4, 5, 6, 7, 8, 12, 16, 24, 36, 48, 60, 72, 84, 96, 108, 120, 132, 144, or 156 weeks or more and about 160, 156, 150, 138, 126, 114, 102, 90, 78, 66, 54, 42, 30, 24, 18, 12 or 6 weeks or less at about 25, 30, 35, 40, 45, 50, 55, 60, 65 or 70°C and about 65, 70, 75, 80 or 85% relative humidity. The conditions may be closed conditions or open conditions. When used in this specification, "closed" conditions refer to conditions in which the lid of the bottle containing the sample is covered or sealed in the stability experiment, and "open" conditions refer to conditions in which the lid is opened.
[0116] The crystalline form of compound (I) disclosed in this specification is stable when exposed under conditions of about 70°C and about 75% relative humidity for about 2 weeks. That is, the crystalline form of compound (I) disclosed in this specification shows excellent storage stability for a long time. In this specification, "stable" means that the increase in impurities is about 1.0, 0.5, 0.4, 0.3, 0.2, 0.1, 0.05, or 0.01% or less compared to the initial amount of impurities. As for the increase in impurities, it is preferably 1.0% or less, more preferably 0.5% or less, more preferably 0.4% or less, more preferably 0.3% or less, more preferably 0.2% or less, more preferably 0.1% or less, further preferably 0.05% or less, and particularly preferably 0.01% or less.
[0117] In certain embodiments, the crystalline form of compound (I) disclosed in this specification may be physically and / or chemically highly pure. In specific embodiments, the crystals disclosed in this specification may be at least about 100, 99, 98, 97, 96, 95, 94, 93, 92, 91, 90, 89, 88, 87, 86, 85, 84, 83, 82, 81 or 80% physically and / or chemically pure. In some embodiments, the crystals disclosed in this specification are substantially pure. When used in this specification, and unless otherwise specified, "substantially pure" means, for example, substantially free of other solid forms and / or other compounds. In certain embodiments, the crystals disclosed herein contain less than about 20%, 15%, 10%, 9%, 8%, 7%, 6%, 5%, 4%, 3%, 2%, 1%, 0.75%, 0.5%, 0.25% or 0.1% by weight of one or more other solid forms and / or other compounds.
[0118] For example, the free form of compound (I) has a type I crystal Figure 1 The powder X-ray diffraction spectrum (CuKα) shown in Fig. Figure 2 Thermogravimetric-differential thermal analysis (TG-DTA) curve is shown.
[0119] Among them, characteristic peaks in the powder X-ray diffraction spectrum of type I crystals of the free form of compound (I) include, as diffraction angles (2θ±0.2°), 6.2°, 6.7°, 8.3°, 8.7°, 9.3°, 9.7°, 11.1°, 13.0°, 13.7°, 15.4°, 16.3°, 16.9°, 17.7°, 18.7°, 19.4°, 20.3°, 25.1°, 25.9°, and 26.5°. More preferably, characteristic peaks in the powder X-ray diffraction spectrum (CuKα) of type I crystals of the free form of compound (I) have diffraction angles (2θ±0.2°) of 6.2°, 6.7°, 8.3°, 8.7°, 9.3°, 9.7°, 11.1°, 13.0°, 13.7°, 15.4°, 16.3°, 16.9°, 17.7°, 18.7°, 19.4°, 20.3°, 25.1°, 25.9°, and 26.5°, when measured by a reflection method.
[0120] In one embodiment of the present invention, the free form I crystal of compound (I) has peaks at at least two diffraction angles (2θ±0.2°) selected from the following (a) and at least two diffraction angles (2θ±0.2°) selected from the following (b) in the powder X-ray diffraction spectrum (CuKα): (a) 6.2°, 9.3°, 9.7°, 11.1°, 15.4° and 25.1°; (b) 6.7°, 8.3°, 8.7°, 13.0°, 13.7°, 16.3°, 16.9°, 17.7°, 18.7°, 19.4°, 20.3°, 25.9° and 26.5°.
[0121] In a preferred embodiment of the present invention, the free form I crystal of compound (I) has peaks at diffraction angles (2θ±0.2°) selected from at least two of the above group (a) and at least two of the above group (b) in a powder X-ray diffraction spectrum. More preferably, the powder X-ray diffraction spectrum has peaks at diffraction angles (2θ±0.2°) selected from at least three of the above group (a) and at least two of the above group (b). More preferably, the powder X-ray diffraction spectrum has peaks at diffraction angles (2θ±0.2°) selected from at least four of the above group (a) and at least two of the above group (b). More preferably, the powder X-ray diffraction spectrum has peaks at diffraction angles (2θ±0.2°) selected from at least five of the above group (a) and at least two of the above group (b). It is particularly preferred that the powder X-ray diffraction spectrum has peaks at all diffraction angles (2θ±0.2°) selected from the above group (a), and has peaks at at least two selected from the above group (b).
[0122] In other embodiments, the type I crystal of the free form of compound (I) in a preferred embodiment of the present invention has peaks at diffraction angles (2θ±0.2°) selected from at least two of the above group (a) in a powder X-ray diffraction spectrum, and has peaks at at least two, preferably at least three, more preferably at least four, more preferably at least five, more preferably at least six, more preferably at least seven, more preferably at least eight, more preferably at least nine, more preferably at least ten, further preferably at least eleven, further preferably at least twelve, and particularly preferably all of the above group (b).
[0123] In other embodiments, the type I crystal of the free form of compound (I) has peaks at diffraction angles (2θ±0.2°) selected from at least 3 of the above group (a) in the powder X-ray diffraction spectrum, and has peaks at at least 2 of the above group (b), preferably at least 3, more preferably at least 4, more preferably at least 5, more preferably at least 6, more preferably at least 7, more preferably at least 8, more preferably at least 9, more preferably at least 10, further preferably at least 11, further preferably at least 12, and particularly preferably all of the above group (b).
[0124] In other embodiments, the type I crystal of the free form of compound (I) has peaks at diffraction angles (2θ±0.2°) selected from at least 4 of the above group (a) in the powder X-ray diffraction spectrum, and has peaks at at least 2 of the above group (b), preferably at least 3, more preferably at least 4, more preferably at least 5, more preferably at least 6, more preferably at least 7, more preferably at least 8, more preferably at least 9, more preferably at least 10, further preferably at least 11, further preferably at least 12, and particularly preferably all of the above.
[0125] In other embodiments, the type I crystal of the free form of compound (I) has peaks at diffraction angles (2θ±0.2°) selected from at least 5 of the above group (a) in the powder X-ray diffraction spectrum, and has peaks at at least 2 of the above group (b), preferably at least 3, more preferably at least 4, more preferably at least 5, more preferably at least 6, more preferably at least 7, more preferably at least 8, more preferably at least 9, more preferably at least 10, further preferably at least 11, further preferably at least 12, and particularly preferably all of the above group (b).
[0126] In other embodiments, the type I crystal of the free form of compound (I) has peaks at all of the diffraction angles (2θ±0.2°) selected from the above group (a) in the powder X-ray diffraction spectrum, and has peaks at at least 2, preferably at least 3, more preferably at least 4, more preferably at least 5, more preferably at least 6, more preferably at least 7, more preferably at least 8, more preferably at least 9, more preferably at least 10, further preferably at least 11, further preferably at least 12, and particularly preferably all of the above group (b).
[0127] The endothermic peak in the thermogravimetric-differential thermal analysis (TG-DTA analysis) curve of the type I crystal of the free form of compound (I) is around 233°C to 237°C, preferably around 235°C.
[0128] The chemical purity of compound (I) in the free form type I crystal is 90% or more, which can be measured by high performance liquid chromatography (HPLC). Preferably, the chemical purity of compound (I) is 95% or more in the free form type I crystal, and more preferably, the chemical purity is 99% or more.
[0129] The free form I crystal of compound (I) may be a single crystal of the free form I crystal or a polymorphic mixture including crystals other than the single crystal, as long as it contains the free form I crystal. Preferably, 90% or more of the free form I crystal is the free form I crystal, and more preferably, 95% or more of the free form I crystal is the free form I crystal.
[0130] The type I crystal of the free form of compound (I) can be obtained by dissolving the crude compound (I) in tetrahydrofuran and adding ethyl acetate. However, in this case, the obtained particle size is likely to be non-uniform. In the obtained non-uniform crystals, for example, it can be seen that there is a difference in the amount of analogs and residual solvent contained in the flaky part that is easily separated by a sieve with an aperture of 340 μm and the powdery part that has passed the sieve. Although both are type I crystals of the free form of compound (I), it is more preferable to produce type I crystals of the free form of compound (I) with a suppressed residual solvent amount, uniform quality and high chemical purity.
[0131] In the industrial production of pharmaceuticals, as shown in the guidelines of ICH, the amount of residual solvent is required to be as small as possible. The limit value of ethyl acetate is required to be 5000ppm or less, the limit value of tetrahydrofuran is required to be 720ppm or less, and the limit value of dimethyl sulfoxide is required to be 5000ppm or less. The residual amount of ethyl acetate is preferably 5000ppm or less, more preferably 4000ppm or less, more preferably 3000ppm or less, and further preferably 2000ppm or less, and particularly preferably 1000ppm or less. The residual amount of tetrahydrofuran is preferably 720ppm or less, more preferably 500ppm or less, and further preferably 300ppm or less. The residual amount of dimethyl sulfoxide is preferably 5000ppm or less, and more preferably 3000ppm or less.
[0132] The free form I crystal of the compound (I) according to the present invention can be produced, for example, by the following method, which comprises: a step (1) of dissolving the compound (I) in a solvent 1 (rich solvent); and a step (2) of adding a solvent 2 (poor solvent) to the solution obtained in the step (1) to obtain a solid compound (I).
[0133] Preferred dissolving solvents (solvent 1) in step (1) include dimethyl sulfoxide and tetrahydrofuran. More preferred is dimethyl sulfoxide. Preferred solvents (solvent 2) added in step (2) include n-heptane, ethyl acetate or 2-propanol when tetrahydrofuran is used in step (1), and water when dimethyl sulfoxide is used in step (1). Preferably, the solvent 1 in step (1) is dimethyl sulfoxide, and the solvent 2 in step (2) is water.
[0134] In step (2), in order to promote crystallization, an appropriate amount of type I crystals of the free form of compound (I) may or may not be added as seed crystals.
[0135] In step (1), the temperature for dissolving compound (I) can be appropriately set. For example, when compound (I) is dissolved in 20 v / w dimethyl sulfoxide, the temperature is preferably room temperature to 70°C.
[0136] When dimethyl sulfoxide is used in step (1), in step (2), the internal temperature is adjusted to room temperature to 70°C and water is added to precipitate type I crystals of the free form of compound (I). The temperature is preferably maintained at 40 to 70°C, more preferably 60 to 70°C.
[0137] The temperature of water when adding water in step (2) is more preferably 40 to 60° C. The amount of water added at this time is preferably 3 v / w or more, more preferably 20 to 25 v / w, based on compound (I).
[0138] In step (2), when water is used, the water can be slowly added dropwise over a period of 0.5 to 6 hours to obtain type I crystals of the free form of compound (I). At this time, as is generally known, increasing the addition rate can yield crystals with a smaller particle size, and conversely decreasing the addition rate can yield crystals with a larger particle size.
[0139] The precipitated crystals can be separated and purified from the suspension containing the crystals by a known separation and purification method such as filtration, washing with water, and drying under reduced pressure.
[0140] For example, the free form II crystal of compound (I) has Figure 3 The powder X-ray diffraction spectrum shown, moreover, has Figure 4 Thermogravimetric-differential thermal analysis (TG-DTA) curve is shown.
[0141] Among them, characteristic peaks in the crystalline powder X-ray diffraction spectrum (CuKα) of the type II crystal of the free form of compound (I) include, as diffraction angles (2θ±0.2°), 6.7°, 7.5°, 10.4°, 12.7°, 13.4°, 14.6°, 16.5°, 17.9°, 18.3°, 19.8°, 20.6°, 21.8°, 22.9°, 26.5°, and 27.9°. More preferably, characteristic peaks in the powder X-ray diffraction spectrum of type II crystals of the free form of compound (I) have diffraction angles (2θ±0.2°) of 6.7°, 7.5°, 10.4°, 12.7°, 13.4°, 14.6°, 16.5°, 17.9°, 18.3°, 19.8°, 20.6°, 21.8°, 22.9°, 26.5°, and 27.9° when measured by a reflection method.
[0142] In one embodiment of the present invention, the free form II crystal of compound (I) has peaks at at least two diffraction angles (2θ±0.2°) selected from the following (a) and at least two diffraction angles (2θ±0.2°) selected from the following (b) in the powder X-ray diffraction spectrum (CuKα): (a) 10.4°, 22.9° and 27.9°; (b) 6.7°, 7.5°, 12.7°, 13.4°, 14.6°, 16.5°, 17.9°, 18.3°, 19.8°, 20.6°, 21.8° and 26.5°.
[0143] In a preferred embodiment of the present invention, the free form II crystal of compound (I) has peaks at diffraction angles (2θ±0.2°) selected from at least two of the above group (a) in a powder X-ray diffraction spectrum, and has peaks at at least two, preferably at least three, more preferably at least four, more preferably at least five, more preferably at least six, more preferably at least seven, more preferably at least eight, more preferably at least nine, more preferably at least ten, further preferably at least eleven, and particularly preferably all of the above group (b). In another embodiment of the present invention, the free form II crystal of compound (I) has peaks at diffraction angles (2θ±0.2°) selected from at least two of the above group (a), ...
[0144] In another embodiment, the type II crystal of the free form of compound (I) has peaks at diffraction angles (2θ±0.2°) of all of the above group (a) in the powder X-ray diffraction spectrum, and has peaks at at least 2, preferably at least 3, more preferably at least 4, more preferably at least 5, more preferably at least 6, more preferably at least 7, more preferably at least 8, more preferably at least 9, more preferably at least 10, further preferably at least 11, and particularly preferably all of the above group (b).
[0145] The endothermic peak in the thermogravimetric-differential thermal analysis (TG-DTA analysis) curve of the type II crystal of the free form of compound (I) is around 232°C to 236°C, preferably around 234°C.
[0146] In one embodiment of the present invention, the free form II crystal of compound (I) can be produced, for example, by the following method, which comprises: adding compound (I) to a solvent to dissolve it (3); and then heating and suspending it (4), and further comprising cooling the solution of compound (I) to crystallize compound (I) (5). In this embodiment, as the solvent in step (3), for example, methanol can be used. Methanol is preferred.
[0147] In step (4), when methanol is used, the suspension heating temperature can be 50° C. to 100° C. and the reaction heating time can be 0.5 to 48 hours. Preferably, the temperature is 50° C. and the reaction time is 22 hours.
[0148] The crystallization of step (5) can be carried out under stirring. In this case, the stirring is carried out using a stirrer, a stirring paddle, etc., as appropriate, depending on the amount of solvent, the size of the reactor, etc. In addition, the stirring operation can also be carried out, for example, by oscillating the reaction vessel, etc. The stirring speed is usually 1 to 600 rpm, preferably 10 to 100 rpm. In step (5), the cooling temperature can be carried out at room temperature, preferably room temperature.
[0149] In addition, the chemical purity of compound (I) in the free-form type II crystal obtained by the above operation is 90% or more, which can be measured by high performance liquid chromatography (HPLC). Preferably, the chemical purity of compound (I) in the free-form type II crystal is 95% or more, and more preferably, the chemical purity is 99% or more.
[0150] The free-form type II crystal of compound (I) may be a single crystal of the free-form type II crystal or a polymorphic mixture including crystals other than the single crystal, as long as it contains the free-form type II crystal. Preferably, 90% or more of the free-form type II crystal is the free-form type II crystal, and more preferably, 95% or more of the free-form type II crystal is the free-form type II crystal.
[0151] For example, the free form of compound (I) has a type III crystal Figure 5 The powder X-ray diffraction spectrum shown, moreover, has Figure 6 Thermogravimetric-differential thermal analysis (TG-DTA) curve is shown.
[0152] Among them, characteristic peaks in the powder X-ray diffraction spectrum (CuKα) of the type III crystal of the free form of compound (I) include, as diffraction angles (2θ±0.2°), 6.8°, 7.5°, 8.8°, 11.7°, 12.9°, 13.9°, 14.9°, 16.7°, 17.8°, 18.8°, 19.7°, 20.7°, 22.0°, 23.4°, 24.2°, 26.2°, and 26.7°. More preferably, characteristic peaks in the powder X-ray diffraction spectrum of type III crystals of the free form of compound (I) have diffraction angles (2θ±0.2°) of 6.8°, 7.5°, 8.8°, 11.7°, 12.9°, 13.9°, 14.9°, 16.7°, 17.8°, 18.8°, 19.7°, 20.7°, 22.0°, 23.4°, 24.2°, 26.2°, and 26.7° when measured by a reflection method.
[0153] In one embodiment of the present invention, the free form III crystal of compound (I) has peaks at at least two diffraction angles (2θ±0.2°) selected from the following (a) and at least two diffraction angles (2θ±0.2°) selected from the following (b) in the powder X-ray diffraction spectrum (CuKα): (a) 11.7°, 23.4° and 24.2°; (b) 6.8°, 7.5°, 8.8°, 12.9°, 13.9°, 14.9°, 16.7°, 17.8°, 18.8°, 19.7°, 20.7°, 22.0°, 26.2° and 26.7°.
[0154] In a preferred embodiment of the present invention, the free form III crystal of compound (I) has peaks at diffraction angles (2θ±0.2°) selected from at least two of the above group (a) in a powder X-ray diffraction spectrum, and has peaks at at least two, preferably at least three, more preferably at least four, more preferably at least five, more preferably at least six, more preferably at least seven, more preferably at least eight, more preferably at least nine, more preferably at least ten, more preferably at least eleven, more preferably at least twelve or more, further preferably at least thirteen, and particularly preferably all of the above group (b). In another embodiment of the present invention, the free form III crystal of compound (I) has peaks at diffraction angles (2θ±0.2°) selected from at least two of the above group (a) in a powder X-ray diffraction spectrum. In another embodiment, the free form III crystal of compound (I) may have peaks at all of the above group (a).
[0155] In another embodiment, the type III crystal of the free form of compound (I) has peaks at diffraction angles (2θ±0.2°) of all of the above group (a) in the powder X-ray diffraction spectrum, and has peaks at at least 2, preferably at least 3, more preferably at least 4, more preferably at least 5, more preferably at least 6, more preferably at least 7, more preferably at least 8, more preferably at least 9, more preferably at least 10, more preferably at least 11, more preferably at least 12, further preferably at least 13, and particularly preferably all of the above group (b).
[0156] The endothermic peak in the thermogravimetric-differential thermal analysis (TG-DTA analysis) curve of the type III crystal of the free form of compound (I) is around 232°C to 236°C, preferably around 234°C.
[0157] In one embodiment of the present invention, the type III crystal of compound (I) can be produced, for example, by the following method, which comprises: adding compound (I) to a solvent and performing heating and reflux step (6); and then, quenching and crystallizing step (7). In this embodiment, as the solvent in step (6), for example, a solvent such as ethanol or 2-methyltetrahydrofuran can be used alone, or a mixed solvent of ethanol and 2-methyltetrahydrofuran can be used. Preferably, ethanol is used.
[0158] The crystallization in step (7) can be carried out under stirring. In this case, the stirring is carried out using a stirrer, a stirring blade, etc., as appropriate depending on the amount of solvent, the size of the reactor, etc. In addition, the stirring operation can also be carried out by, for example, oscillating the reaction container, etc. The stirring speed is usually 1 to 600 rpm, preferably 10 to 100 rpm.
[0159] In addition, the chemical purity of the free-form III-type crystal of compound (I) obtained as described above is 90% or more, which can be measured by high performance liquid chromatography (HPLC). Preferably, the chemical purity of the free-form III-type crystal of compound (I) is 95% or more, and more preferably, the chemical purity is 99% or more.
[0160] The free-form type III crystal of compound (I) may be a single crystal of the free-form type III crystal or a polymorphic mixture including crystals other than the single crystal, as long as it contains the free-form type III crystal. Preferably, 90% or more of the free-form type III crystal is the free-form type III crystal, and more preferably, 95% or more of the free-form type III crystal is the free-form type III crystal.
[0161] The crystals of the hydrochloride of compound (I) have, for example, Figure 7 The powder X-ray diffraction spectrum shown, moreover, has Figure 8 Thermogravimetric-differential thermal analysis (TG-DTA) curve is shown.
[0162] Among them, characteristic peaks in the powder X-ray diffraction spectrum (CuKα) of the hydrochloride crystals of Compound (I) include, as diffraction angles (2θ±0.2°), 6.7°, 7.4°, 11.2°, 12.6°, 14.1°, 16.6°, 20.0°, 21.1°, 22.0°, 22.6°, 23.2°, 24.5°, 26.4°, 28.0°, 30.0°, and 31.6°. More preferably, characteristic peaks in the powder X-ray diffraction spectrum of the crystals of the hydrochloride of Compound (I) have diffraction angles (2θ±0.2°) of 6.7°, 7.4°, 11.2°, 12.6°, 14.1°, 16.6°, 20.0°, 21.1°, 22.0°, 22.6°, 23.2°, 24.5°, 26.4°, 28.0°, 30.0°, and 31.6° when measured by a reflection method.
[0163] The crystal of the hydrochloride of compound (I) involved in the present invention is a crystal having at least 3 peaks selected from the above peaks, for example, a crystal having at least 3 peaks selected from the above peaks, preferably a crystal having at least 4 peaks selected from the above peaks, more preferably a crystal having at least 5 peaks selected from the above peaks, more preferably a crystal having at least 6 peaks selected from the above peaks, more preferably a crystal having at least 7 peaks selected from the above peaks, more preferably a crystal having at least 8 peaks selected from the above peaks, more preferably a crystal having at least 9 peaks selected from the above peaks, more preferably a crystal having at least 10 peaks selected from the above peaks, more preferably a crystal having at least 11 peaks selected from the above peaks, more preferably a crystal having at least 12 peaks selected from the above peaks, more preferably a crystal having at least 13 peaks selected from the above peaks, more preferably a crystal having at least 14 peaks selected from the above peaks, more preferably a crystal having at least 15 peaks selected from the above peaks, and particularly preferably a crystal having all the above peaks.
[0164] The endothermic peak in the thermogravimetric-differential thermal analysis (TG-DTA analysis) curve of the hydrochloride salt crystal of Compound (I) can be around 239°C to 243°C, preferably around 241°C.
[0165] In one embodiment of the present invention, the crystal of the hydrochloride of compound (I) can be prepared, for example, by the following method, which comprises: adding compound (I) to a solvent, adding hydrochloric acid, and stirring at room temperature to perform crystallization step (8). In this embodiment, as the solvent in step (8), for example, ethyl acetate, methanol, ethanol, etc. or a mixed solvent thereof can be used. Preferably, the mixed solvent is ethyl acetate and methanol.
[0166] The crystallization in step (8) can be carried out under stirring. In this case, the stirring is carried out using a stirrer, a stirring blade, etc., as appropriate depending on the amount of solvent, the size of the reactor, etc. In addition, the stirring operation can also be carried out by, for example, oscillating the reaction container, etc. The stirring speed is usually 1 to 600 rpm, preferably 10 to 100 rpm.
[0167] The amount of hydrochloric acid added in step (8) may be 0.9 to 1.1 molar equivalents relative to the amount of compound (I), preferably 1.0 molar equivalent.
[0168] The chemical purity of the hydrochloride crystals of compound (I) obtained as described above is 90% or more, which can be measured by high performance liquid chromatography (HPLC). Preferably, the chemical purity of the hydrochloride crystals of compound (I) is 95% or more, and more preferably, the chemical purity is 99% or more.
[0169] The crystals of the hydrochloride of compound (I) may be single crystals of the hydrochloride or a polymorphic mixture including crystals other than single crystals, as long as they contain crystals of the hydrochloride. Preferably, 90% by weight or more of the crystals are hydrochloride crystals, and more preferably, 95% or more of the crystals are hydrochloride crystals.
[0170] The crystals of the maleate salt of compound (I) have, for example, Fig. 9 The powder X-ray diffraction spectrum shown, moreover, has Fig.10 Thermogravimetric-differential thermal analysis (TG-DTA) curve is shown.
[0171] Among them, characteristic peaks in the powder X-ray diffraction spectrum (CuKα) of the maleate salt crystals of Compound (I) include, as diffraction angles (2θ±0.2°), 6.5°, 9.8°, 12.1°, 13.0°, 13.9°, 14.7°, 15.2°, 15.9°, 17.7°, 18.4°, 19.0°, 20.1°, 20.9°, 21.5°, 22.9°, 23.4°, 25.3°, 28.0°, 29.7°, and 30.8°. More preferably, the characteristic peaks in the powder X-ray diffraction spectrum of the crystals of the maleate salt of compound (I) have diffraction angles (2θ±0.2°) of 6.5°, 9.8°, 12.1°, 13.0°, 13.9°, 14.7°, 15.2°, 15.9°, 17.7°, 18.4°, 19.0°, 20.1°, 20.9°, 21.5°, 22.9°, 23.4°, 25.3°, 28.0°, 29.7°, and 30.8° when measured by a reflection method.
[0172] The crystal of the maleate salt of compound (I) according to the present invention is a crystal having at least 3 peaks selected from the above peaks, for example, a crystal having at least 3 peaks selected from the above peaks, preferably a crystal having at least 4 peaks selected from the above peaks, more preferably a crystal having at least 5 peaks selected from the above peaks, more preferably a crystal having at least 6 peaks selected from the above peaks, more preferably a crystal having at least 7 peaks selected from the above peaks, more preferably a crystal having at least 8 peaks selected from the above peaks, more preferably a crystal having at least 9 peaks selected from the above peaks, more preferably a crystal having at least 10 peaks selected from the above peaks, more preferably a crystal having Crystals having at least 11 peaks selected from the above-mentioned peaks are more preferred, crystals having at least 12 peaks selected from the above-mentioned peaks are more preferred, crystals having at least 13 peaks selected from the above-mentioned peaks are more preferred, crystals having at least 14 peaks selected from the above-mentioned peaks are more preferred, crystals having at least 15 peaks selected from the above-mentioned peaks are more preferred, crystals having at least 16 peaks selected from the above-mentioned peaks are more preferred, crystals having at least 17 peaks selected from the above-mentioned peaks are more preferred, crystals having at least 18 peaks selected from the above-mentioned peaks are more preferred, crystals having at least 19 peaks selected from the above-mentioned peaks are more preferred, and crystals having all of the above-mentioned peaks are particularly preferred.
[0173] The endothermic peak in the thermogravimetric-differential thermal analysis (TG-DTA analysis) curve of the maleate salt of Compound (I) crystals can be around 243°C to 247°C, preferably around 245°C.
[0174] In one embodiment of the present invention, the crystal of the maleate salt of compound (I) can be prepared, for example, by the following method, which includes: adding compound (I) and maleic acid to a solvent, heating and stirring, and obtaining an amorphous body in step (10); then heating the obtained amorphous body under reflux in step (11); then stirring at room temperature, and then cooling on ice for crystallization in step (12). In this embodiment, as the solvent in step (10), for example, chloroform, methanol, etc. or a mixed solvent thereof can be used. Preferably, it is a mixed solvent of chloroform and methanol. In step (11), as the solvent used, for example, acetonitrile can be used. In step (11), it can be carried out at a temperature near the boiling point of the solvent, and when the solvent is acetonitrile, it is preferably 85°C.
[0175] The amount of maleic acid added in step (10) must be the same molar equivalent as the amount of compound (I).
[0176] The crystallization in step (9) may be performed under stirring. In this case, stirring is performed using a stirrer, a stirring blade, etc., as appropriate depending on the amount of solvent, the size of the reaction vessel, etc. The stirring operation may also be performed by, for example, shaking the reaction vessel.
[0177] The chemical purity of the maleate crystals of compound (I) obtained as described above is 90% or more, which can be measured by high performance liquid chromatography (HPLC). Preferably, the chemical purity of the maleate crystals of compound (I) is 95% or more, and more preferably, the chemical purity is 99% or more.
[0178] The maleate crystals of Compound (I) may be single crystals of maleate or a polymorphic mixture including crystals other than single crystals. Preferably, 90% or more of the maleate crystals are maleate crystals, and more preferably, 95% or more of the maleate crystals are maleate crystals.
[0179] An embodiment of obtaining the crystal form (type I crystal, type II crystal, type III crystal) of the free form of the compound (I) of the present invention, the crystal of the hydrochloride salt, and the crystal of the maleate salt is described above, but these are only illustrative. The crystal form (type I crystal, type II crystal, type III crystal) of the free form of the compound (I) of the present invention, the crystal of the hydrochloride salt, and the crystal of the maleate salt are not limited to the crystals obtained by the above-exemplified embodiment. Those skilled in the art can use well-known technical means to manufacture the crystal form (type I crystal, type II crystal, type III crystal) of the free form of the compound (I) of the present invention, the crystal of the hydrochloride salt, and the crystal of the maleate salt.
[0180] As shown in the examples described below, the free form of compound (I) of the present invention, type I crystal, type II crystal, type III crystal, crystal of the hydrochloride of compound (I), and crystal of the maleate of compound (I) have low hygroscopicity and excellent solid stability (storage stability, etc.). It is important for the original drug of a pharmaceutical product and the active ingredient in the pharmaceutical product to have solid stability in both industrial operations and quality maintenance.
[0181] In addition, solvents used in the production of pharmaceuticals are sometimes toxic. From the viewpoint of safety, it is desirable that the amount of residual solvents in the production process be as small as possible. The type I crystal of the free form of compound (I) does not contain residual solvents exceeding the limit value of the ICH (International Conference on Harmonization of Pharmaceuticals in Japan, the United States and Europe) guidelines.
[0182] The free form of compound (I) according to the present invention, namely, type I crystal, type II crystal, type III crystal, hydrochloride crystal and maleate crystal, has excellent antitumor effect and is useful as a pharmaceutical for treating tumors.
[0183] When the free form of compound (I) of type I crystal, type II crystal, type III crystal, hydrochloride crystal, or maleate crystal is used as a medicine, the crystal may be crushed or not, and various administration forms may be adopted according to the purpose of prevention or treatment. Such forms may be, for example, oral preparations such as tablets, capsules, granules, fine granules, powders, and dry syrups; and any of non-oral preparations such as suppositories, inhalants, nasal drops, ointments, patches, and injections, preferably used in oral preparations. These pharmaceutical compositions may be prepared by conventional preparation methods known to those skilled in the art using pharmaceutically acceptable carriers.
[0184] As pharmaceutical carriers, various organic or inorganic carrier substances conventionally used as raw materials for preparations can be used, as excipients, binders, disintegrants, lubricants, coating agents in solid preparations, solvents, solubilizers, suspending agents, isotonic agents, buffers, analgesics, etc. in liquid preparations. In addition, preparation additives such as preservatives, antioxidants, colorants, sweeteners, stabilizers, etc. can also be used as needed.
[0185] Examples of the excipient include lactose, saccharide, D-mannitol, starch, crystalline cellulose, and calcium silicate.
[0186] Examples of the binder include hydroxypropyl cellulose, methyl cellulose, polyvinyl pyrrolidone, powdered sugar, and hypromellose.
[0187] Examples of the disintegrant include sodium starch glycolate, carboxymethylcellulose calcium, cross-linked carboxymethylcellulose sodium, crospovidone, low-substituted hydroxypropyl cellulose, and partially pregelatinized starch.
[0188] Examples of the lubricant include talc, magnesium stearate, sucrose fatty acid esters, stearic acid, and sodium stearyl fumarate.
[0189] Examples of the coating agent include ethyl cellulose, aminoalkyl methacrylate copolymer RS, hypromellose, and white sugar.
[0190] Examples of the solvent include water, propylene glycol, and physiological saline.
[0191] Examples of the solubilizing agent include polyethylene glycol, ethanol, α-cyclodextrin, Macrogol 400, and Polysorbate 80.
[0192] Examples of the suspending agent include carrageenan, crystalline cellulose / sodium carboxymethyl cellulose, and polyoxyethylene hydrogenated castor oil.
[0193] Examples of the isotonic agent include sodium chloride, glycerin, potassium chloride and the like.
[0194] Examples of the pH adjuster / buffer include sodium citrate, hydrochloric acid, lactic acid, phosphoric acid, and sodium dihydrogen phosphate.
[0195] Examples of the analgesic include procaine hydrochloride and lidocaine.
[0196] Examples of the preservative include ethyl paraben, creosol, and benzalkonium chloride.
[0197] Examples of the antioxidant include sodium sulfite, ascorbic acid, and natural vitamin E.
[0198] Examples of the coloring agent include titanium oxide, ferric oxide, food blue No. 1, and copper chlorophyll.
[0199] Examples of flavoring / odor correcting agents include aspartame, saccharin, sucralose, L-menthol, and mint flavor.
[0200] Examples of the stabilizer include sodium pyrosulfite, sodium edetate, isoascorbic acid, magnesium oxide, and butylated hydroxytoluene.
[0201] In the case of preparing a solid preparation for oral administration, an excipient, a binder as required, a disintegrant, a lubricant, a colorant, a flavoring agent, or a odor correcting agent can be added to the free form of compound (I) in the form of type I crystals, type II crystals, type III crystals, hydrochloride crystals, or maleate crystals, and then tablets, coated tablets, granules, powders, capsules, or the like can be prepared by conventional methods.
[0202] The amount of the free form of compound (I) type I crystal, type II crystal, type III crystal, hydrochloride crystal and maleate crystal to be formulated in each dosage unit regimen varies depending on the symptoms of the patient to be administered, the dosage form, etc., and cannot be generalized. Generally, the amount is preferably about 0.05 to 1000 mg for oral preparations, about 0.1 to 500 mg for injections, and about 1 to 1000 mg for suppositories or external preparations per dosage unit regimen.
[0203] In addition, the daily dosage of the free form of compound (I) of the pharmaceutical agent having each dosage regimen, the type I crystal, the type II crystal, the type III crystal, the hydrochloride crystal and the maleate crystal, varies depending on the patient's symptoms, body weight, age, sex, etc., and cannot be generalized. Generally, an adult (weight 50 kg) can be treated with compound (I) or a pharmaceutically acceptable salt thereof at a dosage level of about 20 mg / day, about 40 mg / day, about 60 mg / day, about 80 mg / day, about 100 mg / day, about 200 mg / day, or about 300 mg / day at intervals of administration. The dosage may be about 400 mg / day, about 500 mg / day, about 600 mg / day, about 3000 mg / day, about 2,500 mg / day, about 2,000 mg / day, about 1,500 mg / day, about 1,000 mg / day, about 900 mg / day, about 800 mg / day, about 700 mg / day, or any dosage level within these ranges. It is preferably administered once a day or divided into 2 to 3 times.
[0204] The administration of compound (I) or a pharmaceutically acceptable salt thereof (particularly preferably a hydrochloride or a maleate) can be set to continuous (administered 7 days a week) or intermittent administration, for example, according to the pharmacokinetics and the clearance / accumulation of the drug in a specific subject. In the case of intermittent administration, for example, it can be a regimen of administering for 4 days a week and resting for 3 days (drug withdrawal), or it can be other intermittent administration regimens that are considered appropriate using sound medical judgment, but continuous administration is preferred. Administration can be once a day (QD) or twice or more a day (bid, tid, etc.), preferably in an amount of about 20 to 960 mg / day QD. The daily dose can be administered as a single dose or as divided doses. For example, two tablets containing 40 mg of compound (I) or a pharmaceutically acceptable salt thereof (particularly preferably a hydrochloride or a maleate) can be administered to a subject once a day (QD) at a total dose of 80 mg / day. In one embodiment, two tablets each containing 40 mg of compound (I) or a pharmaceutically acceptable salt thereof (particularly preferably a hydrochloride or a maleate salt) can be administered to a subject twice a day (bid) at a total dose of 160 mg / day. The amount of compound (I) or a pharmaceutically acceptable salt thereof administered is the amount converted to the amount of compound (I).
[0205] Whether continuous or intermittent, administration can be continued for a specific treatment cycle, typically a cycle of at least 28 days, which can be repeated with or without a drug holiday. Longer or shorter cycles such as 14 days, 18 days, 21 days, 24 days, 35 days, 42 days, 48 days, or any range therebetween can also be used. The cycle can be repeated without a drug-free period or with a drug-free period, depending on the subject. Other regimens can also be used depending on the presence or absence of adverse events, the response of the cancer to treatment, the convenience of the patient, etc. "Adverse event" refers to an undesirable or unexpected disease or symptom thereof in a patient to whom a drug is administered. It is not important whether there is a causal relationship with the drug. In the case of intermittent administration, for example, administration can be performed on days 1, 3, 5, 7, 9, 11, 13, 15, 17, 19, 21, 23, 25, 27, on days 1, 4, 8, 11, 15, 19, 23, 27, and on days 1, 3, 5, 8, 10, 12, 15, 17, 19, 22, 24, 26 in a 28-day cycle.
[0206] The powder X-ray diffraction measurement method of the crystal of the compound (I) according to the present invention can be measured by a reflection method.
[0207] Generally speaking, the morphology of many grains in the sample holder tends to impart selective orientation to the sample. Selective orientation in the sample affects the intensity of various reflections, resulting in reflections being observed to be stronger in some cases and weaker in others than would be expected from a completely unoriented sample.
[0208] Example Hereinafter, examples are given to explain the present invention in more detail, but the present invention is not limited by these examples. The present invention is fully described according to the examples, but it should be understood that various changes and / or modifications can be made by those skilled in the art. Therefore, as long as such changes and / or modifications do not depart from the scope of the present invention, they are included in the present invention.
[0209] <Reagents and assay methods> Unless otherwise specified, commercially available reagents were used in the Examples. NMR spectra were obtained using AL400 (400 MHz; JEOL). When tetramethylsilane was contained in the deuterated solvent, tetramethylsilane was used as an internal reference. Otherwise, the non-deuterated proton peak remaining in the NMR solvent was used as an internal reference. The total δ value was expressed in ppm.
[0210] The meanings of the abbreviations are as follows.
[0211] s: Single peak d: Twin Peaks t: Three Peaks dd: double double peaks m: multiple peaks brs: broad single peak DMSO-d6: deuterated dimethyl sulfoxide CDCl3: deuterated chloroform Powder X-ray diffraction measurement In the powder X-ray diffraction, an appropriate amount of a test substance is lightly pulverized in an agate mortar as required, and then measured under the following test conditions.
[0212] Device: PANalytical Empyrean Target: Cu X-ray output setting: 40mA, 45kV Scanning range: 2.0~40.0° Step size: 0.026° Measurement method: Reflection method The operation of the devices involving data processing follows the methods and steps indicated by each device.
[0213] Furthermore, the values obtained from various spectra may vary slightly depending on the direction of crystal growth, particle size, measurement conditions, etc. Therefore, these values should not be strictly interpreted.
[0214] Thermogravimetric-differential thermal analysis (TG-DTA) The TG-DTA measurement was performed under the following test conditions.
[0215] Device: Hitachi High-Tech TG / DTA7200 Sample: about 5 mg Sample container: Aluminum Heating rate: 10℃ / min to 300℃ Atmosphere gas: air Nitrogen flow rate: 100mL / min The operation of the devices involving data processing follows the methods and steps indicated by each device.
[0216] Residual solvent determination The residual solvent was measured under the following test conditions.
[0217] Measured objects: Ethyl acetate, tetrahydrofuran 〈GC (gas chromatography) conditions〉 Device: Shimadzu GC-2010 Plus Detector: FID Chromatographic column: Inert Cap-5 Science (0.53mm×30m, 5μm) Column temperature: 40°C for 10 minutes, increase the temperature by 2°C per minute to 110°C, then increase the temperature by 30°C per minute to 250°C, and maintain for 15 minutes Injection temperature: 260℃ Detection temperature: 260℃ Atmosphere gas: He Line speed: 28cm / min Gas flow rate: 400mL / min Helium flow rate: 50mL / min Auxiliary speed: 50mL / min Auxiliary gas: He 〈HS Conditions〉 HS oven temperature: 80°C HS needle temperature: 90°C Transmission line temperature: 100°C Measurement time: 30min Compression time: 3 / min Pulling up time: 0.2 / min Injection time: 0.1 / min GC cycle time: 80 / min Measured object: Dimethyl sulfoxide 〈GC (gas chromatography) conditions〉 Detector: FID Chromatographic column: Inert Cap Pure-WAX, GLScience (30m×0.53mm×5μm) Column temperature: 35°C for 5 minutes, increase the temperature by 5°C per minute to 80°C, then increase the temperature by 3°C per minute to 170°C, then increase the temperature by 20°C per minute to 230°C, and maintain for 10 minutes Injection temperature: 240℃ Detection temperature: 240℃ Atmosphere gas: He Flow rate: 28cm / min Split ratio: 10:1 Injection volume: 1μL Detection gas flow: H2: 50ml / min; Air: 400mL / min; N2: 45mL / min The operation of the devices including data processing follows the methods and steps indicated by the respective devices.
[0218] Example 1 Preparation of Type I Crystals of Free Form of Compound (I) Compound (I) (11.7 g) synthesized according to the method described in International Publication No. 2017 / 200087 (Example 32) was suspended in ethyl acetate (110 mL), stirred at 100°C for 4 hours, and then stirred at room temperature for 18 hours. The suspension was filtered, and the obtained powder (10.4 g) was resuspended in ethyl acetate (220 mL). The suspension was stirred at 100°C for 5 hours, and then stirred at room temperature for 9 hours. The suspension was filtered to obtain type I crystals (9.37 g) of the free form of compound (I) with a yield of 80.1% and a chemical purity of 97.31%.
[0219] The obtained type I crystal of compound (I) 1 The H-NMR spectrum is shown below.
[0220] 1 H-NMR (DMSO-D6) δ: 8.23 (1H, s), 7.92 (1H, d, J = 8.8 Hz), 7.09 (1H,d, J = 8.8 Hz), 6.45 (1H, t, J = 5.2 Hz), 4.49 (2H, d, J = 13.2 Hz), 3.22(5H, m, 3.29-3.13), 2.71 (2H, t, J = 6.7 Hz), 1.93 (2H, d, J = 12.0 Hz), 1.76(2H, m, 1.82-1.70), 1.39 (6H, s), 1.03 (9H, s) In addition, according to 1 The H-NMR spectrum showed that the residual solvent contained about 5700 ppm of ethyl acetate. 1 The residual amount of solvent in the H-NMR spectrum was calculated by converting the integrated value ratio of the peak derived from compound (I) to the solvent peak into a weight ratio using the molecular weight and by using the formula: weight of solvent÷(weight of compound (I)+weight of solvent).
[0221] The powder X-ray diffraction spectrum and thermogravimetric-differential thermal analysis (TG-DTA analysis) curve of the obtained free-form type I crystal are shown below.
[0222] Powder X-ray diffraction spectrum: expressed in Figure 1 .
[0223] The characteristic diffraction angles are shown below.
[0224] Characteristic diffraction angle (2θ±0.2°): 6.2°, 6.7°, 8.3°, 8.7°, 9.3°, 9.7°, 11.1°, 13.0°, 13.7°, 15.4°, 16.3°, 16.9°, 17.7°, 18.7°, 19.4°, 20.3°, 25.1°, 25.9°, 26.5° The peaks are shown in the following table (Table 1).
[0225] [Table 1] Thermogravimetric-differential thermal analysis (TG-DTA) curve: Figure 2 .
[0226] Preparation Example 1 Preparation of Type I Crystal of Free Form of Compound (I) The free form I crystal of compound (I) can also be produced by the following method.
[0227] Compound (I) (6.0 g) synthesized according to the method described in International Publication No. 2017 / 200087 (Example 32) was dissolved in a mixed solvent of tetrahydrofuran (42 mL) and ethyl acetate (210 mL) in an oil bath at 110°C under heating reflux for 1 hour. The internal temperature at this time was 75°C. The oil bath was removed and stirred at room temperature for 3 hours to precipitate crystals of compound (I). The internal temperature of the suspension at this time was 30°C. The suspension was filtered and dried under reduced pressure at 65°C for 10 hours to obtain type I crystals of the free form of compound (I) (3.83 g, yield 64%).
[0228] The obtained compound (I) (20.00 g) was suspended in dimethyl sulfoxide (400 mL, 20 v / w) and stirred. After degassing at room temperature for 5 minutes, nitrogen was sealed in. The obtained suspension was heated and stirred in an oil bath at 65°C for 25 minutes to dissolve the crude compound (I) to form a light yellow solution. The internal temperature at this time was 59°C.
[0229] The solution was clarified and filtered through a glass fiber filter (Glass-Fiber Filter, Whatman, GF / B, Φ60 mm), and the container was rinsed with 20 mL (1 v / w) of dimethyl sulfoxide. The temperature of the filtrate was 40°C.
[0230] The filtrate obtained by filtration was heated and stirred again in an oil bath at 65°C until the internal temperature reached 58°C, and then water (420 mL, 21 v / w) was added to precipitate crystals. Crystals of compound (I) began to precipitate about 4 hours after the dropwise addition of water (70 mL, 3.5 v / w), and the internal temperature at this time was about 63°C.
[0231] Then, water (350 mL, 17.5 v / w) was added dropwise for 70 minutes to allow further crystal precipitation.
[0232] After the addition of water was completed, the mixture was further stirred at an internal temperature of 67°C for 1 hour, and then the suspension was allowed to cool to room temperature for 3 hours while stirring.
[0233] The obtained suspension was filtered through Kiriyama filter paper (2 sheets, No. 3, Φ95 mm (upper) and No. 4, Φ95 mm (lower)), and the wet crystals of compound (I) collected by filtration were washed with water (300 mL, 15 v / w).
[0234] The obtained wet crystals of compound (I) crystal I were dried under reduced pressure at 70°C for 14 hours to obtain pale yellow free form of compound (I) type I crystals (19.13 g, yield 96%, chemical purity 99.12%). 1 The H-NMR spectrum calculated that the residual solvent contained about 2400 ppm of dimethyl sulfoxide, but no ethyl acetate and tetrahydrofuran were detected. The amount of residual solvent was calculated in the same way as in Example 1. The residual solvent was then analyzed by GC, which showed dimethyl sulfoxide (2629 ppm), tetrahydrofuran (ND), and ethyl acetate (ND). ND means below the limit of quantification, and the values below the limit of quantification of each solvent in the GC analysis were set to 235 ppm for dimethyl sulfoxide, 900 ppm for ethyl acetate, and 145 ppm for tetrahydrofuran.
[0235] Example 2 Preparation of Type II Crystals of Free Form of Compound (I) 40 mL of methanol was added to 2.00 g of compound (I) synthesized according to the method described in International Publication No. 2017 / 200087, and the mixture was heated, suspended and stirred at 50°C for 22 hours. Then, the mixture was cooled and stirred at room temperature for 2 hours, and the solid was filtered out. The mixture was dried under reduced pressure at 40°C for 20 hours to obtain 1.883 g of type II crystals of the free form of compound (I). (Yield 94%)
[0236] The obtained free form II crystal of compound (I) 1 The H-NMR spectrum is shown below.
[0237] 1H-NMR (DMSO-d6) δ: 8.22 (1H, s), 7.91 (1H, d, J = 8.8 Hz), 7.09 (1H,d, J = 8.8 Hz), 6.41 (1H, t, J = 5.2 Hz), 4.49 (2H, d, J = 13.6 Hz), 3.30-3.14 (5H, m), 2.71 (2H, t, J = 6.7 Hz), 1.92 (2H, d, J = 12.0 Hz), 1.80-1.70(2H, m), 1.39 (6H, s), 1.03 (9H, s). The powder X-ray diffraction spectrum and thermogravimetric-differential thermal analysis (TG-DTA analysis) curve of the obtained free-form type II crystal are shown below.
[0238] Powder X-ray diffraction spectrum: expressed in Figure 3 .
[0239] The characteristic diffraction angles are shown below.
[0240] Characteristic diffraction angle (2θ±0.2°): The diffraction angle (2θ±0.2°) is 6.7°, 7.5°, 10.4°, 12.7°, 13.4°, 14.6°, 16.5°, 17.9°, 18.3°, 19.8°, 20.6°, 21.8°, 22.9°, 26.5°, and 27.9°.
[0241] The peaks are shown in the following table (Table 2).
[0242] [Table 2] Thermogravimetric-differential thermal analysis (TG-DTA) curve: Figure 4 .
[0243] Example 3 Preparation of Type III Crystals of Free Form of Compound (I) Add 28 mL of ethanol to 500 mg of compound (I) synthesized according to the method described in International Publication No. 2017 / 200087, heat under reflux at an internal temperature of around 78°C, and quench with a dry ice-methanol bath after confirming dissolution. (The internal temperature was brought to -2°C in about 1 minute after the start of cooling) After confirming the precipitation of crystals, switch to an ice bath, stir at an internal temperature of around 0°C for 30 minutes, and filter out the solid. Dry under reduced pressure at 40°C for 20 hours to obtain 347 mg of type III crystals of the free form of compound (I). (Yield 69%)
[0244] The obtained free form III crystal of compound (I) 1 The H-NMR spectrum is shown below.
[0245] 1 H-NMR (DMSO-d6) δ: 8.23 (1H, s), 7.92 (1H, d, J = 8.8 Hz), 7.10 (1H,d, J = 8.8 Hz), 6.44 (1H, t, J = 5.2 Hz), 4.50 (2H, d, J = 13.6 Hz), 3.41-3.14 (5H, m), 2.73 (2H, t, J = 6.7 Hz), 1.94 (2H, d, J = 12.0 Hz), 1.85-1.72(2H, m), 1.40 (6H, s), 1.05 (9H, s). The powder X-ray diffraction spectrum and thermogravimetric-differential thermal analysis (TG-DTA analysis) curve of the obtained free-form III-type crystal are shown below.
[0246] Powder X-ray diffraction spectrum: expressed in Figure 5 .
[0247] The characteristic diffraction angles are shown below.
[0248] Characteristic diffraction angle (2θ±0.2°): The diffraction angles (2θ±0.2°) are 6.8°, 7.5°, 8.8°, 11.7°, 12.9°, 13.9°, 14.9°, 16.7°, 17.8°, 18.8°, 19.7°, 20.7°, 22.0°, 23.4°, 24.2°, 26.2°, and 26.7°.
[0249] The peaks are shown in the following table (Table 3).
[0250] [Table 3] Thermogravimetric-differential thermal analysis (TG-DTA) curve: Figure 6 .
[0251] Example 4 Preparation of Crystals of Hydrochloride Salt of Compound (I) After adding 3 ml of ethyl acetate and 3 ml of methanol to compound (I) (202 mg) synthesized according to the method described in International Publication No. 2017 / 200087 and stirring, 71 ul of 5M hydrochloric acid aqueous solution (1 molar equivalent relative to compound (I)) was added and stirred at room temperature for 2 hours. The solid was filtered and dried under reduced pressure to obtain crystals of the hydrochloride of compound (I) (161 mg). (Yield 75%)
[0252] The obtained crystals of the hydrochloride of compound (I)1 The H-NMR spectrum is shown below.
[0253] 1 H-NMR (DMSO-d6) δ: 11.10 (1H, s), 8.96 (1H, br s), 8.22 (1H, s), 7.96 (1H, d, J = 8.8 Hz), 7.18 (1H, d, J = 8.8 Hz), 6.79 (1H, br s), 4.48(2H, d, J = 13.6 Hz), 3.35-3.19 (5H, m), 2.71 (2H, t, J = 6.7 Hz), 1.95-1.75(4H, m), 1.39 (6H, s), 1.31 (9H, s). The powder X-ray diffraction spectrum and thermogravimetric-differential thermal analysis (TG-DTA analysis) curve of the obtained hydrochloride crystals are shown below.
[0254] Powder X-ray diffraction spectrum: expressed in Figure 7 .
[0255] The characteristic diffraction angles are shown below.
[0256] Characteristic diffraction angle (2θ±0.2°): 6.7°, 7.4°, 11.2°, 12.6°, 14.1°, 16.6°, 20.0°, 21.1°, 22.0°, 22.6°, 23.2°, 24.5°, 26.4°, 28.0°, 30.0°, 31.6° Thermogravimetric-differential thermal simultaneous measurement was measured according to the experimental conditions of TG-DTA measurement described in the above "<Reagents and Measurement Method>", except that the temperature was raised to 400°C at a rate of 10°C / min.
[0257] The peaks are shown in the following table (Table 4).
[0258] [Table 4] Thermogravimetric-differential thermal analysis (TG-DTA) curve: Figure 8 .
[0259] Example 5 Preparation of Crystals of Maleate Salt of Compound (I) Compound (I) (2.0 g) synthesized according to the method described in International Publication No. 2017 / 200087 was dissolved by adding 20 mL of chloroform / methanol (9 / 1). Maleic acid 405 mg (1 molar equivalent relative to compound (I)) was added, heated and stirred at 45°C, and after confirming dissolution, the solvent was distilled off under reduced pressure. The residue was dried under reduced pressure at 40°C to obtain 2.43 g of amorphous maleate (yield 101%, CHCl3 residual). Acetonitrile 200 mL was added to 500 mg of amorphous maleate, heated and refluxed to dissolve it. Cooled at room temperature and stirred, ice-cooled after the internal temperature reached near room temperature, stirred for 1 hour, and the solid was filtered out. Drying under reduced pressure at 40°C obtained 332 mg of maleate crystals (yield 66%).
[0260] The obtained crystals of the maleate salt of compound (I) 1 The H-NMR spectrum is shown below.
[0261] 1 H-NMR (DMSO-d6) δ: 11.12 (1H, s), 8.39(1H, s), 7.99 (1H, d, J = 8.8Hz), 7.14 (1H, d, J = 8.8 Hz), 6.55 (1H, t, J = 5.2 Hz), 6.00 (2H, s), 4.50(2H, d, J = 13.6 Hz), 3.60-3.07 (7H, m), 1.91 (2H, d, J = 12.0 Hz), 1.80-1.70(2H, m), 1.39 (6H, s), 1.03 (9H, s). The powder X-ray diffraction spectrum and thermogravimetric-differential thermal analysis (TG-DTA analysis) curve of the obtained maleate salt crystals are shown below.
[0262] Powder X-ray diffraction spectrum: expressed in Fig. 9 .
[0263] The characteristic diffraction angles are shown below.
[0264] Characteristic diffraction angle (2θ±0.2°): 6.5°, 9.8°, 12.1°, 13.0°, 13.9°, 14.7°, 15.2°, 15.9°, 17.7°, 18.4°, 19.0°, 20.1°, 20.9°, 21.5°, 22.9°, 23.4°, 25.3°, 28.0°, 29.7°, 30.8°.
[0265] The peaks are shown in the following table (Table 5).
[0266] [Table 5] Thermogravimetric-differential thermal simultaneous measurement was measured according to the experimental conditions of TG-DTA measurement described in the above "<Reagents and Measurement Method>", except that the temperature was raised to 400°C at a rate of 10°C / min.
[0267] Thermogravimetric-differential thermal analysis (TG-DTA) curve: Fig.10 .
[0268] Comparative Example 1 Preparation of Crystals of 1 / 2 Malate of Compound (I) To 1.00 g of compound (I) synthesized according to the method described in International Publication No. 2017 / 200087, add 75 mL of 1-propanol, heat and stir, and dissolve at an internal temperature of about 75°C. Add 129 mg (0.55 eq.) of L-malic acid and wash with 5 mL of 1-propanol. Raise the temperature to an internal temperature of 90°C, stir at this temperature for 30 minutes, and then cool by leaving at room temperature, and slowly cool and stir. Crystals precipitate at about 70°C, stir for 30 minutes while maintaining this temperature, then cool, stir at below 10°C overnight, and filter out the solid. Dry under reduced pressure at 40°C for 2 days to obtain 1.00 g of 1 / 2 malate. (Yield 90%)
[0269] The obtained 1 / 2 malate of compound (I) 1 The H-NMR spectrum is shown below.
[0270] 1 H-NMR (DMSO-d6) δ: 8.22 (1H, s), 7.94 (1H, d, J = 8.8 Hz), 7.11 (1H,d, J = 8.8 Hz), 6.54 (1H, t, J = 5.2 Hz), 4.49 (2H, d, J = 12.8 Hz), 3.85-3.80 (0.5H, m), 3.37-3.16 (5H, m), 2.88 (2H, br s), 2.51-2.26 (1H, m ), 1.93-1.72 (4H, m ), 1.41 (6H, s), 1.15 (9H, s). The powder X-ray diffraction spectrum and thermogravimetric-differential thermal analysis (TG-DTA analysis) curve of the obtained 1 / 2 malate of Compound (I) are shown below.
[0271] Powder X-ray diffraction spectrum: expressed in Fig.11 .
[0272] The characteristic diffraction angles are shown below.
[0273] Characteristic diffraction angle (2θ±0.2°): 6.1°, 7.1°, 10.0°, 11.2°, 17.2°, 19.6°, 16.6°, 25.2° Thermogravimetric-differential thermal analysis (TG-DTA) curve: Fig.12 .
[0274] Comparative Example 2 Preparation of Crystals of Acetate Salt of Compound (I) To 1.00 g of compound (I) synthesized according to the method described in International Publication No. 2017 / 200087, 1 mL of butyl acetate and 998 uL of acetic acid (1 molar equivalent relative to compound (I)) were added, and the mixture was stirred at room temperature to dissolve.
[0275] Heat to 50°C, add 9 mL of butyl acetate, stir for 1 hour, solid precipitates. Cool to room temperature and stir, then stir for 1 hour under ice cooling, filter out solid. Dry under reduced pressure at 40°C for 20 hours to obtain 693 mg of acetate. (Yield 63%)
[0276] The acetate of the obtained compound (I) 1 The H-NMR spectrum is shown below.
[0277] 1 H-NMR (DMSO-d6) δ: 8.22 (1H, s), 7.91 (1H, d, J = 8.8 Hz), 7.09 (1H,d, J = 8.8 Hz), 6.53 (1H, t, J = 5.2 Hz), 4.48 (2H, d, J = 12.8 Hz), 3.30-3.13 (5H, m), 2.74 (2H, t, J = 6.7 Hz), 1.88-1.7 (7H, m), 1.38 (6H, s), 1.05(9H, s). The powder X-ray diffraction spectrum and thermogravimetric-differential thermal analysis (TG-DTA measurement) curve of the acetate of the obtained compound (I) are shown below.
[0278] Powder X-ray diffraction spectrum: expressed in Fig.13 .
[0279] The characteristic diffraction angles are shown below.
[0280] Characteristic diffraction angle (2θ±0.2°): 11.2°, 11.5°, 12.6°, 13.3°, 15.4°, 15.8°, 17.1°, 17.7°, 18.2°, 18.8°, 19.9°, 21.1°, 21.7°, 22.0°, 23.2°, 23.4°, 23.8°, 26.2°, 26.9°, 27.8° Thermogravimetric-differential thermal analysis (TG-DTA) curve: Fig.14 .
[0281] Test Example 1 Solid Stability Test The storage stability of the free form of Compound (I), Type I crystal, Type II crystal and Type III crystal obtained by the production method described in Examples 1, 2 and 3 was tested under the following conditions.
[0282] Storage conditions: 70℃ / 75%RH (open system and closed system) Measurement point: 2 weeks Storage capacity: about 50mg Storage container: brown glass bottle The powder X-ray diffraction measurement of the sample after storage was measured by the above method. About 1 mg of the sample was weighed and dissolved in about 5 mL of a water / acetonitrile mixed solution (1:1), and 5 μL of the solution was accurately weighed and analyzed by HPLC according to the following method for changes in the amount of analogs (the amount of substances detected other than compound (I)).
[0283] Column: InertSustain C18, 4.6×150mm, 3μm Column temperature: 40°C Column flow rate: 1.0mL / min Mobile phase: A: 10 mM phosphate buffer (pH 5.5) / acetonitrile (9:1); B: acetonitrile Detection UV: 220nm gradient: As a result, the free-body type I crystal, type II crystal and type III crystal did not show any change in the powder X-ray diffraction pattern, and were determined to be extremely stable crystals. In addition, as shown in Table 6 below, the amount of analogs after storage was small for any of the crystals, and no change in appearance was observed.
[0284] [Table 6] Test Example 2 Dynamic moisture adsorption and desorption test VTI-SA+ (TA Instruments) was used in the test. About 10 mg of each of the free-body type I crystal, free-body type II crystal, and free-body type III crystal were weighed and placed in a dish. While confirming that the weight change is within 0.0100% within 5 minutes, the temperature was raised to 60°C by 1 degree per minute. In the case of weight change, the temperature was maintained for a maximum of 5 hours before proceeding to the next step. Then, the temperature was lowered to 25°C, and the humidity was raised from 5% RH to 95% RH, and then lowered to 5% RH. At this time, while confirming that the weight change is within 0.00100% within 5 minutes, humidity was applied at a weight of 5% RH. In the case of weight change, the humidity was maintained for a maximum of 2 hours before proceeding to the next step.
[0285] like Fig.15 , Fig.16 , Fig.17 As shown, it was confirmed that the free-form type I crystal, the free-form type II crystal, and the free-form type III crystal had low hygroscopicity. In particular, it was found that the free-form type I crystal and the free-form type III crystal showed excellent low hygroscopicity.
[0286] Test Example 3 Thermal stability test Thermal stability tests were conducted using the free-form type I crystal, free-form type II crystal, and free-form type III crystal obtained by the methods described in Examples 1, 2, and 3 above.
[0287] The powder X-ray diffraction measurement was performed at 25°C, and the temperature was raised to 50°C in 30 minutes, and then the powder X-ray diffraction measurement was performed. The temperature was further raised to 210°C at 10°C / 10 minutes, and then the powder X-ray diffraction measurement was performed, and the temperature was lowered to 25°C in 30 minutes, and then the powder X-ray diffraction measurement was performed. In the obtained spectrum, it was confirmed whether there was a new peak appearing or decreasing in the spectrum that was the subject before and after the start of the test.
[0288] The results of the thermal stability tests of the free-form type I crystal, free-form type II crystal, and free-form type III crystal at 25°C and 210°C are shown in Fig.18 , 19 , 20, 21, 22, 23.
[0289] As a result, the free-body type I crystal did not change its crystal form when heated up to 210° C., confirming that it was stable. On the other hand, the free-body type II crystal and the free-body type III crystal showed new peaks upon heating, indicating that the crystal form was not maintained.
[0290] Test Example 4 Solid Stability Test The storage stability of the hydrochloride crystals, maleate crystals, 1 / 2 malate crystals and acetate crystals of Compound (I) obtained by the methods described in Example 4, Example 5, Comparative Example 1 and Comparative Example 2 was tested under the conditions of Test Example 1.
[0291] As a result, no change in the powder X-ray diffraction pattern was confirmed for the crystals of the hydrochloride salt of compound (I) and the crystals of the maleate salt. It was determined that the crystals were extremely stable. In addition, as shown in Tables 7 and 8 below, the amount of analogs of the crystals of the hydrochloride salt of compound (I) and the crystals of the maleate salt after storage was very small, and no change in appearance was observed.
[0292] As shown in Tables 9 and 10 below, the crystals of 1 / 2 malate and acetate of Compound (I) showed no change in appearance after storage, but contained a large amount of analogs.
[0293] [Table 7] [Table 8] [Table 9] [Table 10] Test Example 5 Dynamic moisture adsorption and desorption test The storage stability of the hydrochloride crystals, maleate crystals, 1 / 2 malate crystals, and acetate crystals of Compound (I) obtained by the methods described in Example 4, Example 5, Comparative Example 1, and Comparative Example 2 was tested under the conditions of Test Example 2.
[0294] The results are shown in Fig.24 , Fig.25 , Fig.26 , Fig. 27 It was confirmed that the crystals of the maleate salt exhibited low hygroscopicity, and that the crystals of the hydrochloride salt exhibited hygroscopicity lower than 1 / 2 of that of the crystals of the malate salt.
Claims
1. A type I crystal of a free form of 4-(4-(3-((2-(tert-butylamino)ethyl)amino)-6-(5-(trifluoromethyl)-1,3,4-oxadiazol-2-yl)pyridin-2-yl)piperidin-1-yl)-5,5-dimethyl-5H-pyrrolo[2,3-d]pyrimidin-6(7H)-one, characterized in that: In the powder X-ray diffraction spectrum (CuKα), it has peaks at at least two diffraction angles (2θ±0.2°) selected from the following (a), and at least two diffraction angles (2θ±0.2°) selected from the following (b): (a) 6.2°, 9.3°, 9.7°, 11.1°, 15.4° and 25.1°; (b) 6.7°, 8.3°, 8.7°, 13.0°, 13.7°, 16.3°, 16.9°, 17.7°, 18.7°, 19.4°, 20.3°, 25.9° and 26.5°.
2. The free-body type I crystal according to claim 1, characterized in that: In the powder X-ray diffraction spectrum (CuKα), it has peaks at at least three diffraction angles (2θ±0.2°) selected from the following (a), and at least four diffraction angles (2θ±0.2°) selected from the following (b): (a) 6.2°, 9.3°, 9.7°, 11.1°, 15.4° and 25.1°; (b) 6.7°, 8.3°, 8.7°, 13.0°, 13.7°, 16.3°, 16.9°, 17.7°, 18.7°, 19.4°, 20.3°, 25.9° and 26.5°.
3. The free-body type I crystal according to claim 1, characterized in that: In the powder X-ray diffraction spectrum (CuKα), there are peaks at the following diffraction angles (2θ±0.2°): 6.2°, 6.7°, 8.3°, 8.7°, 9.3°, 9.7°, 11.1°, 13.0°, 13.7°, 15.4°, 16.3°, 16.9°, 17.7°, 18.7°, 19.4°, 20.3°, 25.1°, 25.9° and 26.5°.
4. The free-body type I crystal according to claim 1, characterized in that: This is a crystal having a powder X-ray diffraction spectrum substantially the same as the powder X-ray diffraction spectrum shown in FIG. 1 .
5. The free-body type I crystal according to claim 1, characterized in that: It has an endothermic peak with a peak temperature of approximately 235° C. in simultaneous thermogravimetric-differential thermal analysis (TG-DTA analysis).
6. A pharmaceutical composition, characterized in that: A type I crystal comprising the free form according to any one of claims 1 to 5.
7. The method for producing the free-body type I crystal according to claim 1, characterized in that: include: A step of dissolving 4-(4-(3-((2-(tert-butylamino)ethyl)amino)-6-(5-(trifluoromethyl)-1,3,4-oxadiazol-2-yl)pyridin-2-yl)piperidin-1-yl)-5,5-dimethyl-5H-pyrrolo[2,3-d]pyrimidin-6(7H)-one in solvent 1; and A step of adding solvent 2 to the obtained solution to obtain 4-(4-(3-((2-(tert-butylamino)ethyl)amino)-6-(5-(trifluoromethyl)-1,3,4-oxadiazol-2-yl)pyridin-2-yl)piperidin-1-yl)-5,5-dimethyl-5H-pyrrolo[2,3-d]pyrimidin-6(7H)-one.
8. The method according to claim 7, characterized in that: Solvent 1 is dimethyl sulfoxide, solvent 2 is water, Alternatively, solvent 1 is tetrahydrofuran, and solvent 2 is n-heptane, ethyl acetate or 2-propanol.
9. The method according to claim 7, characterized in that: Solvent 1 is dimethyl sulfoxide, and solvent 2 is water.
10. The free-body type I crystal according to claim 1, characterized in that: The method comprises dissolving 4-(4-(3-((2-(tert-butylamino)ethyl)amino)-6-(5-(trifluoromethyl)-1,3,4-oxadiazol-2-yl)pyridin-2-yl)piperidin-1-yl)-5,5-dimethyl-5H-pyrrolo[2,3-d]pyrimidin-6(7H)-one in dimethyl sulfoxide; The obtained solution is added with water to obtain 4-(4-(3-((2-(tert-butylamino)ethyl)amino)-6-(5-(trifluoromethyl)-1,3,4-oxadiazol-2-yl)pyridin-2-yl)piperidin-1-yl)-5,5-dimethyl-5H-pyrrolo[2,3-d]pyrimidin-6(7H)-one, and the obtained product is crystallized.
11. A type II crystal of a free form of 4-(4-(3-((2-(tert-butylamino)ethyl)amino)-6-(5-(trifluoromethyl)-1,3,4-oxadiazol-2-yl)pyridin-2-yl)piperidin-1-yl)-5,5-dimethyl-5H-pyrrolo[2,3-d]pyrimidin-6(7H)-one, characterized in that: In the powder X-ray diffraction spectrum (CuKα), it has peaks at at least two diffraction angles (2θ±0.2°) selected from the following (a), and at least two diffraction angles (2θ±0.2°) selected from the following (b): (a) 10.4°, 22.9° and 27.9°; (b) 6.7°, 7.5°, 12.7°, 13.4°, 14.6°, 16.5°, 17.9°, 18.3°, 19.8°, 20.6°, 21.8° and 26.5°.
12. The free-body type II crystal according to claim 11, characterized in that: In the powder X-ray diffraction spectrum (CuKα), it has peaks at at least three diffraction angles (2θ±0.2°) selected from the following (a), and at least four diffraction angles (2θ±0.2°) selected from the following (b): (a) 10.4°, 22.9° and 27.9°; (b) 6.7°, 7.5°, 12.7°, 13.4°, 14.6°, 16.5°, 17.9°, 18.3°, 19.8°, 20.6°, 21.8° and 26.5°.
13. The free-body type II crystal according to claim 11, characterized in that: In the powder X-ray diffraction spectrum (CuKα), there are peaks at the following diffraction angles (2θ±0.2°): 6.7°, 7.5°, 10.4°, 12.7°, 13.4°, 14.6°, 16.5°, 17.9°, 18.3°, 19.8°, 20.6°, 21.8°, 22.9°, 26.5° and 27.9°.
14. The free-body type II crystal according to claim 11, characterized in that: This is a crystal having a powder X-ray diffraction spectrum substantially the same as the powder X-ray diffraction spectrum shown in FIG. 3 .
15. The free-body type II crystal according to claim 11, characterized in that: It has an endothermic peak with a peak temperature of approximately 234° C. in simultaneous thermogravimetric-differential thermal analysis (TG-DTA analysis).
16. A pharmaceutical composition, characterized in that: A type II crystal comprising the free form according to any one of claims 11 to 15.
17. A type III crystal of a free form of 4-(4-(3-((2-(tert-butylamino)ethyl)amino)-6-(5-(trifluoromethyl)-1,3,4-oxadiazol-2-yl)pyridin-2-yl)piperidin-1-yl)-5,5-dimethyl-5H-pyrrolo[2,3-d]pyrimidin-6(7H)-one, characterized in that: In the powder X-ray diffraction spectrum (CuKα), it has peaks at at least two diffraction angles (2θ±0.2°) selected from the following (a), and at least two diffraction angles (2θ±0.2°) selected from the following (b): (a) 11.7°, 23.4° and 24.2°; (b) 6.8°, 7.5°, 8.8°, 12.9°, 13.9°, 14.9°, 16.7°, 17.8°, 18.8°, 19.7°, 20.7°, 22.0°, 26.2° and 26.7°.
18. The free-body type III crystal according to claim 17, characterized in that: In the powder X-ray diffraction spectrum (CuKα), it has peaks at three diffraction angles (2θ±0.2°) selected from the following (a), and at least four diffraction angles (2θ±0.2°) selected from the following (b): (a) 11.7°, 23.4° and 24.2°; (b) 6.8°, 7.5°, 8.8°, 12.9°, 13.9°, 14.9°, 16.7°, 17.8°, 18.8°, 19.7°, 20.7°, 22.0°, 26.2° and 26.7°.
19. The free-body type III crystal according to claim 17, characterized in that: In the powder X-ray diffraction spectrum (CuKα), there are peaks at the following diffraction angles (2θ±0.2°): 6.8°, 7.5°, 8.8°, 11.7°, 12.9°, 13.9°, 14.9°, 16.7°, 17.8°, 18.8°, 19.7°, 20.7°, 22.0°, 23.4°, 24.2°, 26.2° and 26.7°.
20. The free-body type III crystal according to claim 17, characterized in that: This is a crystal having a powder X-ray diffraction spectrum substantially the same as the powder X-ray diffraction spectrum shown in FIG. 5 .
21. The free-body type III crystal according to claim 17, characterized in that: It has an endothermic peak with a peak temperature of approximately 234° C. in simultaneous thermogravimetric-differential thermal analysis (TG-DTA analysis).
22. A pharmaceutical composition, characterized in that: A type III crystal comprising the free form according to any one of claims 17 to 21.
23. A crystal of the hydrochloride salt of 4-(4-(3-((2-(tert-butylamino)ethyl)amino)-6-(5-(trifluoromethyl)-1,3,4-oxadiazol-2-yl)pyridin-2-yl)piperidin-1-yl)-5,5-dimethyl-5H-pyrrolo[2,3-d]pyrimidin-6(7H)-one, characterized in that: In the powder X-ray diffraction spectrum (CuKα), it has peaks at at least three diffraction angles (2θ±0.2°) selected from the following diffraction angles: 6.7°, 7.4°, 11.2°, 12.6°, 14.1°, 16.6°, 20.0°, 21.1°, 22.0°, 22.6°, 23.2°, 24.5°, 26.4°, 28.0°, 30.0° and 31.6°.
24. The hydrochloride crystal of claim 23, characterized in that: In the powder X-ray diffraction spectrum (CuKα), there are peaks at the following diffraction angles (2θ±0.2°): 6.7°, 7.4°, 11.2°, 12.6°, 14.1°, 16.6°, 20.0°, 21.1°, 22.0°, 22.6°, 23.2°, 24.5°, 26.4°, 28.0°, 30.0° and 31.6°.
25. The hydrochloride crystal of claim 23, characterized in that: This is a crystal having a powder X-ray diffraction spectrum substantially the same as the powder X-ray diffraction spectrum shown in FIG. 7 .
26. The hydrochloride crystal of claim 23, characterized in that: It has an endothermic peak with a peak temperature of approximately 241° C. in simultaneous thermogravimetric-differential thermal analysis (TG-DTA analysis).
27. A pharmaceutical composition, characterized in that: A crystal comprising the hydrochloride according to any one of claims 23 to 26.
28. A crystal of maleate of 4-(4-(3-((2-(tert-butylamino)ethyl)amino)-6-(5-(trifluoromethyl)-1,3,4-oxadiazol-2-yl)pyridin-2-yl)piperidin-1-yl)-5,5-dimethyl-5H-pyrrolo[2,3-d]pyrimidin-6(7H)-one, characterized in that: In the powder X-ray diffraction spectrum (CuKα), it has peaks at at least three diffraction angles (2θ±0.2°) selected from the following diffraction angles: 6.5°, 9.8°, 12.1°, 13.0°, 13.9°, 14.7°, 15.2°, 15.9°, 17.7°, 18.4°, 19.0°, 20.1°, 20.9°, 21.5°, 22.9°, 23.4°, 25.3°, 28.0°, 29.7° and 30.8°.
29. The crystal of maleate salt according to claim 28, characterized in that: In the powder X-ray diffraction spectrum (CuKα), there are peaks at the following diffraction angles (2θ±0.2°): 6.5°, 9.8°, 12.1°, 13.0°, 13.9°, 14.7°, 15.2°, 15.9°, 17.7°, 18.4°, 19.0°, 20.1°, 20.9°, 21.5°, 22.9°, 23.4°, 25.3°, 28.0°, 29.7° and 30.8°.
30. The crystal of maleate salt according to claim 28, characterized in that: This is a crystal having a powder X-ray diffraction spectrum substantially the same as the powder X-ray diffraction spectrum shown in FIG. 9 .
31. The crystal of maleate salt according to claim 28, characterized in that: It has an endothermic peak with a peak temperature of approximately 245° C. in simultaneous thermogravimetric-differential thermal analysis (TG-DTA analysis).
32. A pharmaceutical composition, characterized in that: A crystal comprising the maleate salt according to any one of claims 28 to 31.
Citation Information
Patent Citations
Novel 5h-pyrrolo[2,3-d]pyrimidin-6(7H)-one derivative
WO2017200087A1